Mechanism of Gegen Qinlian Decoction in the treatment of diabetic cataract based on network pharmacology and experimental validation - Juanjuan Xia; Xin Wang; Xiaomei Fu; Weihong Zhong; Wenting Wu; Liping Yu; Ruixiang Xu; Jing Tang; Ting Gui; Jing Liu; Shuhong Peng; Weifeng Zhu (Tissue and Cell, 2027)

Delayed flooding after green manure incorporation enhances microbial necromass formation and stabilization in paddy soils - Zhengbo Ma; Danna Chang; Qingxu Ma; Haoran Fu; Jinxin Sun; Ting Liang; Cheng Cai; Sheng Tang; Guopeng Zhou; Davey L. Jones; Wolfgang Wanek; Qing Zhang; et al. (Soil Biology and Biochemistry, 2026)

New polyoxygenated fatty acid ester and other constituents from Dendrobium nobile Lindl. and their chemotaxonomic significance - Ting Chen; Dan Zhang; Xiujuan Fu; Siwei Chen; Hui Lei; Xiaoxu Bi (Biochemical Systematics and Ecology, 2026)

Trading time for space: a new approach to investigate the EEG neural mechanisms of fine motor brain based on ICA-optimized traceability network analysis - Anmin Gong; Huijie Man; Xinyu Shi; Sinan Li; Xiuyan Hu; Bowen Gong; Ting Shi; Yunfa Fu (Cognitive Neurodynamics, 2026)

Contrasting redox-related physiological responses associated with HaGATA23 and HaGATA36 during Orobanche cumana parasitism in sunflower (Helianthus annuus L.) - Yan Fu; Ting Zhou; Shuo Zhang; Shuowei Su; Lei Shen; Ying Li; Wenya Zhang; Ahsan Ayyaz; Hongju Sun; Ling Xu (Plant Science, 2026)

Diverse bioactive metabolites from Callicarpa longifolia var. floccosa: terpenoids, polyketide, and callilongiflocin A as a potent anti-inflammatory diterpenoid targeting IL-17/TNF-α/MAPK signaling with anti-psoriatic activity - Ting Liu; Xiao-Lu Wu; Lian-Chun Li; Lan-Fang Tan; De-Sheng Ning; Yu-Xia Fu; Zheng-Hong Pan (Phytochemistry, 2026)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Intermittent organophosphate pesticide exposure induces hepatic injury in goats with subclinical fatty liver via immune activation and energy metabolism reprogramming - Dechun Chen; Tianjun Yang; Ting Zhao; Anzhu Li; Qingjia Lin; Xinying Zhou; Huanrong Zhang; Jian Fu; Falong Yang; Haifeng Liu (Environmental Pollution, 2026)

Bioinspired orientation-regulated conductive hydrogels with hierarchical lamellar architecture for synergistic mechanical and electrical robustness - Tianhao Yu; Chao Rong; Ting Su; Shijia Wan; Bowei Zhang; Yabin Yan; Fu-Zhen Xuan (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Indoor environmental quality of underground spaces: Multi-dimensional assessment and interaction effects in a renovated air-raid shelter bookstore in transition season - Ran Cheng; Ting Fu; Hong Hu; Shan Gao; Chi Feng (Building and Environment, 2026)

Persistent carbon composition converges across vegetated and unvegetated coastal soils despite contrasting stabilization pathways - Yuan Li; Joeri Kaal; Chuancheng Fu; Dongdong Zhang; Peter I. Macreadie; Ting Wang; Lin Zeng; Feilong Hu; Guangxuan Han; Yongming Luo (Water Research, 2026)

Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

Identification and functional validation of a beta-amyrin synthase for Clinopodiside A biosynthesis in medicinal plant Clinopodium chinense - Qianlan Liu; Chun Liu; Zitong Tan; Yu Fu; Ting He; Yi Yuan; Yuling Tai (Plant Science, 2026)

Preparation and performance analysis of a novel composite dust suppressant considering wind and train vibration effects - Hao-kui Wang; Ming-yi Chen; Zi-ting Pei; Fu-chao Tian; Yue Ren; Xing-jun Ma; Ming-xin Li (Journal of Environmental Chemical Engineering, 2026)

New insights into the changes of structure-activity characteristics from dark beer melanoidins through different chemical treatments and in vitro digestion and fermentation - Yaning Nie; Ting Xia; Yihong Fu; Yixie Chen; Jun Wang; Nannan Zhang; Shuxia Huang; Junhong Yu; Min Wang (Food Research International, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Honokiol targets cyclophilin D and blocks mitochondrial DNA release to inhibit microglial NLRP3 inflammasome activation and alleviate neurodegeneration in Parkinson's disease models - Qinglin Gan; Yingtong Xian; Ting Zhou; Xiaolong Fu; Shiyi Gou; Shaoyu Zhou (Chemico-Biological Interactions, 2026)

Tetrahydroisoquinoline alkaloids from the fruits of Piper nigrum and their chemotaxonomic significance - Yan Li; Bin Chen; Wei-Cheng Hu; Fu Li; Ting Shen (Biochemical Systematics and Ecology, 2026)

Unveiling the pathogenesis and therapeutic strategies of Alzheimer’s disease through cuproptosis - Shuangfeng Xu; Jing Mu; Zhifeng Wang; Jiao Yang; Daman Tian; Ting Shi; Junfeng Lan; Pengfen He; Zhihui Hao; Youchuan Fu; Liwei Xing; Jianzhou Ye; et al. (BioMetals, 2026)

EXtreme Gradient Boosting for Lithology Identification with Well Logs: A Case Study from the Salt Lake Area, Eastern Qaidam Basin, China - Zhong-yi Duan; Fu-long Zheng; Hang-yu Yue; Jia-pan Yan; Kun Xiao; Ting-yan Zhang; Jia-dong Yan (Applied Geophysics, 2026)

Neonatal Malnutrition Diagnoses Align Differently With Body Composition Outcomes: A Retrospective Cohort Analysis Evaluating 3 Different Growth Standards - Louise Perna; Kera McNelis; Jacqueline Wessel; Stephanie Merlino Barr; Chunyan Liu; Shelley Ehrlich; Jae H. Kim; Ting Ting Fu (Journal of the Academy of Nutrition and Dietetics, 2026)

Coordination-induced electronic reconstruction of natural polyphenols enables catalytic photodynamic antimicrobial amplification - Jiazhen Wang; Menghuan Sun; Ting Du; Bangfeng Fu; Ruyue Zhang; Mingrui Zhang; Jing Sun; Wentao Zhang; Jianlong Wang (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Multi-omics, machine learning, and molecular simulation identify CD44 as a candidate target in endocrine-disrupting chemical–associated thyroid cancer progression - Yifan Hu; Keshu Liu; Ting Chen; Zhizhen He; Shuang Li; Wu Hu; Qiuyang Fu; Xiong Chen (Molecular Diversity, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

In vivo spatiotemporal fate of nanoparticle-incorporated dissolving microneedles: nanoparticle size effects - Ting Zhou; Yanping Fu; Kaitlyn Wu; Ziyang Zheng; Xinyu Wen; Guanlin Wang; Siyuan Peng; Xin Pan; Chuanbin Wu; Zhengwei Huang; Guilan Quan (Drug Delivery and Translational Research, 2026)

Retraction notice to “Influence of the morphological change in natural Asian dust during transport: A modeling study for a typical dust event over northern China” [Sci. Total Environ. 739 (2020) 139791] - Yu Tian; Zhe Wang; Xiaole Pan; Jie Li; Ting Yang; Dawei Wang; Xiaoyong Liu; Hang Liu; Yuting Zhang; Shandong Lei; Yele Sun; Pingqing Fu; et al. (Science of The Total Environment, 2026)

Time-dependent citrate-mediated precipitation inhibition in uranium column leaching: Mechanistic insights into pore evolution and uranium migration - Xiaowei Zhou; Jing Sun; Qian Li; Guangyue Li; Shangze Li; Ling Xiao; Hong Shu; Haiying Fu; Ting Li; Yongdong Wang; Zhao Cui; Guosen Xie (Journal of Hazardous Materials, 2026)

Fabrication of a flower-like MgIn2S4/BiOBr Z-scheme heterostructure via an in situ route for organic pollutant photodegradation - Jingyi Li; Huanli Wang; Jingchuan Fu; Chenyu Zhu; Ting Liu; Wei Xu; Huawei Zhang (Journal of Cleaner Production, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Green-synthesized ε-polylysine/zein nanocomplexes as safe antimicrobials: Applications and metabolomic mechanisms in grape preservation - Chunli Fang; Ruiqi Zhu; Jia Wei; Nan Wei; Ting Feng; Jun Ma; Zhinan Fu; Bin Wu; Xuhong Guo (Food Chemistry, 2026)

Tunable shell thickness in analyte-responsive core-shell plasmonic arrays at liquid-liquid interface for dual-mode optical sensing - Tianhao Chen; Xiwang Hou; Ruoshui Liu; Ting Lyu; Wenqin Fu; Minggang Zhao; Ye Ma (Food Chemistry, 2026)

Particle-Size Control of Radionuclide Enrichment and Environmental Risk Pathways in Slurry from the Wandan Mud Volcano - Chih-Chung Lin; Yu-Sheng Wang; Wei-Hsiang Huang; Ting-Chien Chen; Yuan-Fu Lu (Environmental Pollution, 2026)

An optimized inflow turbulence generator for LES of wind effects on high-rise buildings using MINSRFG method - Yangxue Wang; Shidi Wang; Ting Deng; Jiyang Fu; Ching Tai Ng (Engineering Structures, 2026)

New healthcare management framework informed by peri-body perception space: a perspective - Chaoqun Dong; Yan Ji; Ruzhen Luo; Xuemei Fu; Zhongmin Fu; Yingying Huang; Ting Yi; Zhifei Chen; Yiwen Hu; Ziqi Chen; Shimeng Dai; Guangming Tao; et al. (EPMA Journal, 2026)

A new species and a newly recorded species of the genus Hua (Gastropoda: Semisulcospiridae) from the Chishui River, Yunnan, China - Jian-Fu Wei; Yuan-Chao Chen; Xue-Hua Li; Guang-Can Zhou; Qi-Yan Zhu; Ting-Song Yu; Jun-Xing Yang; Xiao-Ai Wang (Molluscan Research, 2026)

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

AI-guided mining and characterization of plantaricin LP2150: inhibitory mechanism against Shewanella putrefaciens and preservation of large yellow croaker (Larimichthys crocea) - Jie Yang; Yangfan Fu; Shuang Kong; Xiucheng Shang; Meizhong Hu; Antuo Hu; Saikun Pan; Ting Nie; Yanan Liu (Food Control, 2026)

Study on the along-wind response and aerodynamic mechanism of supertall buildings under setback tapering and rotation designs - Yangxue Wang; Ting Deng; Ching Tai Ng; Jiyang Fu (Engineering Structures, 2026)

Enhancing the spatio-temporal resolution of urban PM2.5 mapping via large-scale mobile monitoring data and machine learning - Rui Xu; Dawen Yao; Ruhui Cao; Yixin Fu; Ting Gan; Yonghong Liu (Atmospheric Pollution Research, 2026)

Evaluation and comparison of TCR repertoire differences between patients with cervical cancer and healthy individuals - Wenwen Gao; Cong Wang; Jiawen Jia; Yiqian Li; Ting Li; Ling Liu; Yi Zhang; Haibin Yu; Cuiping Yang; Xiaoli Fu; Yongbin Chen; Yan Cheng (Science China Life Sciences, 2026)

Autotetraploid induction and one-step regeneration, and transcriptomic analysis in Dendrobium officinale - Cong-Dan Zheng; Jun-Yu Su; Shang-Yan Fu; Jie-Mei Deng; Zi-Ting Zhu; Heng-Yu Huang; Yuan-Zhong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Functional Characterization of CLE Peptides in Cotton Root Development Reveals GhCLE47 as a Key Regulator of Auxin-Mediated Root Architecture - Gai-Yuan Hu; Peng Liao; Xin-Yao Jiang; Ying-Chao Tang; Ting-Wan Li; Yang Li; Fu-Chun Xu; Zhen-Nan Zhang (Journal of Plant Growth Regulation, 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Decline of beneficial microbes and proliferation of latent pathogens: Key drivers of postharvest disease in citrus - Jianghua Chen; Mengting Xu; Ting Zhu; Ziyi Yang; Juan Liu; Jie Duan; Yang Lin; Xiao Yu; Daohong Jiang; Yanping Fu (Postharvest Biology and Technology, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

New alkaloids from the marine-derived fungus Penicillium sp. SWMU-WZ04-5 and their cytotoxic activity - Sijing Liu; Jinghao Cui; Mengyu Zhang; Ting Chen; Fengjian Lan; Xiujuan Fu; Siwei Chen; Dan Zhang; Ying Zhang; Hui Lei (Phytochemistry Letters, 2026)

Inhibition and metabolic toxicity regulation of niacin on Staphylococcus aureus and its application in meat product preservation - Lei Tian; Xiangqi Bai; Chunyang Huang; Min Li; Ting Zhou; Chunling Zhang; Ying Yu; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; et al. (International Journal of Food Microbiology, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Sediment–water interface reoxygenation by NO3–LDH promotes tetracycline degradation in sediments and modulates antibiotic resistance gene dynamics - Zeyu Li; Jincheng Fu; Jiacheng Hu; Ting Li; Yin Xu (Environmental Research, 2026)

Genome-wide analysis of sunflower (Helianthus annuus) and Orobanche cumana reveals HaEXLA2 and HaEXLB2 as negative regulators of lignin-based resistance - Lei Shen; Yi Duan; Ying Li; Wenya Zhang; Yan Fu; Ting Zhou; Hongju Sun; Ahsan Ayyaz; Ling Xu (Plant Cell Reports, 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Cuproptosis: a novel mechanism and 3PM-oriented therapeutic strategy for cancer - Ding Yang; Wei-Ting Hu; Miao Li; Fang-Qing Shen; Hao-Yu Wang; Jin-Ying Ye; Fu-Lu Ren; Yun Wang (EPMA Journal, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Synergistic effects of Ni2P/Ni5P4 heterostructure and N-doped carbon for enhanced asymmetric supercapacitor performance - Minyi Lin; Ting Hu; Wei Qiu; Yuanxiang Fu; Yongbo Wu; Yuhong Luo; Xiaoming Lin (Chemical Engineering Journal, 2026)

Sulfobetaine-modified palladium nanozyme for alleviating ulcerative colitis via RONS scavenging and microbiome remodeling - Chaoyue Sun; Min Feng; Ting Yang; Hongjia Song; Jinbin Wang; Chang Peng; Haiyan Zhang; Xiangli Zhong; Zhao Fu (Chemical Engineering Journal, 2026)

Enzyme mimics catalytic process in organic pollutants treatment: Applications, mechanisms, and challenges - Ting Peng; Sha Long; Enxu Liu; Xuran Liu; Dongbo Wang; Yukui Fu; Jin Huang (Chemical Engineering Journal, 2026)

LDH/sponge promotes nitrogen and phosphorus removal in SBBR reactors by enhancing biofilm development and microbial functional: Evidence from metagenomic analysis - Jiani Zhang; Zeyu Li; Jincheng Fu; Ting Li; Yujiao Wang; Yin Xu (Chemical Engineering Journal, 2026)

RCTUnet: a deep learning model for crop-residue-soil image segmentation and crop residue cover extraction - Ting Li; Yang Liu; Haikuan Feng; Meiyan Shu; Hao Yang; Yuanyuan Fu; Xin Xu; Yinghao Lin; Hongbo Qiao; Wei Guo; Xinming Ma; Lei Shi; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Wide range lower atmosphere duct parameter inversion from automatic identification system signals using hybrid strategy artificial lemming algorithm - Ting Ting Fu; Hao Cha; Yu Luo; Hong Wei Fu; Yu Zhang; Bin Tian (Frontiers in Marine Science, 2026)
Lower atmospheric ducts significantly alter the propagation of Very High Frequency (VHF) and higher-frequency electromagnetic waves in the marine boundary layer, critically impacting radar and communication systems. Effective duct monitoring is essential for optimizing these systems. Emerging, more economical remote sensing approaches—such as satellite-based remote sensing and the monitoring of ubiquitous shipborne Automatic Identification System (AIS) signals—provide promising alternatives for large-scale, cost-effective data acquisition compared to the traditional monitoring methods (e.g., radiosondes, lidars). To tackle the challenges posed by the inversion of lower-atmospheric duct with large vertical extent and high parameter dimensionality, robust and accurate parameter inversion techniques are urgently required. To address this, this study proposes the Hybrid Strategy Artificial Lemming Algorithm (HSALA), an intelligent optimization framework for prior-information-free duct inversion. Comparative inversion simulations of HSALA, the standard Artificial Lemming Algorithm (ALA), Particle Swarm Optimization (PSO), Grey Wolf Optimization (GWO), and Harris Hawk Optimization (HHO) demonstrate HSALA’s superior accuracy and stability under ideal, noise-free conditions. It achieves a mean inversion accuracy exceeding 98% and reduces the root mean square error (RMSE) by over 80% on average in noise-free conditions across 30 trials. Further validation using field-collected AIS data yields a mean parameter inversion accuracy of approximately 81.4%, confirming the method’s practical applicability while highlighting the performance gap introduced by real-world complexities such as signal noise, model bias and atmospheric horizontal inhomogeneity. This method provides a promising and effective solution for operational duct monitoring using AIS signals, bridging a significant gap toward real-time, large-range inversion. The insights from the field validation underscore the value of this approach for engineering practice and outline a clear path for future refinement.

Accelerated degradation of antibiotics via UV irradiation in the presence of chlorite: roles of reactive species, degradation pathways, and toxicity - Yu-qiong Gao; Xue-ting Ren; Yang-yang Liu; Ju-xiang Chen; Fu-xiang Tian; Nai-yun Gao; Cong Li (Journal of Water Process Engineering, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Harnessing Machine learning to quantify ecosystem services in coastal Wetlands: A case study of the Bohai economic Rim - Ting Lu; Ya Ping Wang; Jiyuan Jin; Shibing Zhu; Jianhua Gao; Hu Ding; Qinglong Wu; Fu Wang; Chao Gao (Ecosystem Services, 2026)

Construction of elastic superhydrophobic multiscale cellulose fiber aerogels with tunable pore size for efficient separation of oil-water mixtures - Lili Wang; Ronglan Wu; Daning Lang; Jun Yang; Ting Zhao; Chao Yang; Lu Wang; Jihong Fu (Carbohydrate Polymers, 2026)

Development Mechanism of Axial Chain Rockbursts Induced by the Amphibolite Band in a Granite Tunnel Excavated by TBM: A Case Study - Tao Ma; Xia-Ting Feng; Zhibin Yao; Chengxiang Yang; Lei Hu; Wei Zhang; Yongrun Xiong; Lianjie Fu (Rock Mechanics and Rock Engineering, 2026)

Recent technology advances and commercialization on green methanol synthesis - Bingyan Sun; Marc Mate; Tan Li; Tianfu Zhang; Ting Fan; Di Fu; Kaige Wang (Resources, Conservation and Recycling, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Hyaluronic acid–butyrate conjugates for barrier restoration in atopic dermatitis: CD44-mediated retention and inflammation-responsive release - Ting Liu; Guorong Chen; Chunxiang Zhao; Jiajia Fu; Agui Xie; Beilei Cai; Luyong Zhang; Huixia Lv (Carbohydrate Polymers, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Petrology, geochemistry and geochronology of the Kekeya ash (SW Tarim Basin): Implications for its origin and provenance - Jia-Jun Mo; Yu-Ting Zhong; Man Wang; Le Zhang; Qiong Wu; Qiang Ma; He Wang; Jahandar Ramezani; Xiao-Long Huang; Fu-Yuan Wu; Yi-Gang Xu (Lithos, 2026)

Impacts of the mega cascade reservoirs on riverine hydrothermal regimes based on deep learning - Meixiu Yu; Jinjie Guan; Jianyun Zhang; Junliang Jin; Qingshe Meng; Hanlin Song; Zixuan Xu; Xiaolong Liu; Jiayi He; Ting Fu (Journal of Hydrology, 2026)

Dynamic response reconstruction of high-rise buildings under hazards using a Pyramid-LSTM-Attention network - Haoran Pan; Fan Jiang; Jia Guo; Ting Deng; Jiyang Fu (Engineering Structures, 2026)

Physicochemical and mineralogical constraints on the ecological rehabilitation of coal mine waste - Hui Wu; Songlin Wu; Chenxing Wang; Yige Zhang; Suixiaochen Chen; Wei Fu; Ting-Shan Chan; Duminda Vidana Gamage; Baodong Chen (Plant and Soil, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Copper bioremediation by Trichoderma spp. - Kehe Fu; Lili Fan; Ting Huang; Zhenying Huang; Ying Gao; Dehui Zheng (Biologia, 2026)

Persteroid, a new steroid from the marine-derived fungus Penicillium sp. ZYX-Z-143 - Lu-Ting Dai; Li Yang; Zi-Peng Wang; Jiao-Cen Guo; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Natural Product Research, 2026)

The effects of thermal stress on the morphology, physiological functions, gut microbiota, and metabolism of Penaeus vannamei under seawater and low-salinity conditions - Xuan-yi Zhu; Yi-fu Xing; Xiao-ting Zheng; Jian-hua Huang; Jian Qin; Jia-song Zhang (Aquaculture, 2026)

The novel model INEDM and two traditional models for estimating the carrying capacity of Hong Kong oyster (Crassostrea hongkongensis) in two aquaculture systems in Guangdong Province of China [Aquaculture Volume 609, July 2025.] - Xing-Chi Guo; Wen-Ding Liu; Xiao-Yan Ye; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2026)

Automatic detection of equatorial plasma bubbles using deep neural networks - Ting Zhang; Yifu Luo; Bin Zhang; Fang Jiang; Tianfang Wang; Si Xiao; Xuesong Bai; Liping Fu (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Antibacterial mechanism of vitamin C against Staphylococcus aureus, reduction of toxicity of metabolites and its application in pasteurized milk - Lei Tian; Chunyang Huang; Xing Liu; Yuxin Zhang; Ting Zhou; Ying Yu; Chunling Zhang; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; et al. (International Journal of Food Microbiology, 2026)

The role of geography and regional climate in shaping the chemical profiles and biological potentials of Citrus essential oils - Wenbin Xiao; Jiajing Guo; Yanfang Liao; Yanjiao Fu; Zixuan Li; Tongping Zhang; Ting Liu; Yangbo Xiao; Xuebo Shang; Zhipeng Gao; Yang Shan (Food Chemistry, 2026)

Byakangelicol Alleviates Ischemic Brain Injury by Inhibiting Microglial Activation and Oxidative Stress - Xiao Wan Wang; Yan Qiong Fu; Zhuo Li Li; Ting Li; Hui Lan Wang; Yu Zheng; Chan Zhang; Miaolin Zeng; Chan Li; Dewei Xie; Bai Hui Chen (Molecular Neurobiology, 2026)

Seasonal divergence in the sensitivity of carbon and water fluxes to climate variability in terrestrial ecosystems - Ting Wang; Zheng Fu; David Makowski; Guopeng Liang; Hongxiao Jin; Fangyue Zhang (Agricultural and Forest Meteorology, 2026)

Using UAV multispectral image data to monitor the nitrogen status of head cabbage shoots in the Liupan Mountain area of China - Shuai Wang; Long-Guo Wu; Hua Ma; Kelsang Choron; Fu-Shun Zheng; Zhong-Ting Song; Cui Yin; Hong-Yan Zhu; Peng-Yuan Lv; Yun-e Cao (International Journal of Remote Sensing, 2025)

Multidimensional mechanistic analysis elucidates spermatogenesis disruption induced by bisphenol S - Lei Xu; Bin Huang; Shengliang Gu; Yitao Xing; Fugang Zhang; Wei Fu; Ting Chen; Zhuojun Yuan; Guozheng Qin (Reproductive Toxicology, 2025)

An innovative dual-driven strategy to accelerate and strengthen TGase-induced pea protein gelation via static magnetic field and arabinoxylan pretreatments - Zuwei Yu; Yuxuan Fu; Jiaxin Wei; Ting Yang; Kai Hu; Jingyi Wang (Innovative Food Science & Emerging Technologies, 2025)

Investigation of microstructural characteristics and methane desorption in coal using surfactant treatment - Chen Ming-yi; Pei Zi-ting; Hu Shi-bo; Su Wei-wei; Tian Fu-chao; Zhang Xue-jie (Fuel, 2025)

Neurophysiological and multimodal sensory evaluation of baijiu and food pairing liking - Yu Fu; Cheng Wang; Guoliang He; Shaohui Fan; Deliang Wang; Gaochong Lv; Lucas P.J.J. Noldus; Ting Jiang; Jie Huangfu (Food Research International, 2025)

Covalent engineering of pectin-whey protein isolate conjugates enhances mucoadhesion and bioaccessibility of curcumin microparticles: Strategic impacts of crosslinking modalities - Haifeng Wang; Ting Fang; Ying Chen; Jiang Mou; Teng Li; Yuying Fu; Yun Zhai (Food Chemistry, 2025)

Bioactive pterostilbene encapsulated in zein via an in-situ co-precipitation strategy for efficient antimicrobial and fruit preservative - Chunli Fang; Zhinan Fu; Nan Wei; Jia Wei; Shuying Li; Ting Feng; Zicheng Tan; Junyou Wang; Bin Wu; Xuhong Guo (Food Hydrocolloids, 2025)

Enhanced degradation of pharmaceutical contaminants by medium-pressure UV irradiation in the presence of nitrate: Reactive species, toxicity and DBPs formation - Xiang-mei Zhong; Xiang Fu; Yu-qiong Gao; Yang-yang Liu; Xue-ting Ren; Ji-yue Li; Lei Li; Nai-yun Gao (Environmental Research, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Morphology steering enables efficient ternary organic solar cells via acceptor-phase crystallization control - Shaopeng Fu; Ting Xie; Yanfei Shi; Xingpeng Liu; Jiangang Liu; Jianfeng Li (Chemical Engineering Journal, 2025)

An investigation of localized entropy driven cathode electrolyte interphase to a one-step complete deprotonation of ethylene carbonate on Ni-rich layered material of lithium-ion battery - Laurien Merinda; Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Chusnul Khotimah; Han-Pin Hsieh; Jeng-Kuei Chang; Shu-Chih Haw; Chih-Wen Pao; Jeng-Lung Chen; Qunjie Xu; et al. (Chemical Engineering Journal, 2025)

Synergistic performance enhancements of shear stiffening gel via dynamic-covalent copolymerization and carbon nanotube integration - Ting Fan; Yuanqing Li; Yu Zhu; Yuqin Mao; Ning Hu; Pei Huang; Shaoyun Fu (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Correction: Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2025)

On the perturbation potential energy in the synergistic effect of ENSO and South China Sea summer monsoon on the Indian Ocean dipole development - Yazhou Zhang; Yulian Fu; Bin Zuo; Jianping Li; Yina Diao; Ting Liu; Xin Qi; Haili Wang (Climate Dynamics, 2025)

Long-term fertilization causes differential nitrogen utilization efficiency by influencing function genes of nitrogen cycle and species richness in farmland - Yueyue Xu; Xian Liu; Ting Pan; Zeyu Liu; Fu Chen; Juanling Wang; Xuefang Huang (Agriculture, Ecosystems & Environment, 2025)

Logging intensity and biome type mediate the effects of forest logging on soil greenhouse gas emissions - Chenjun Du; Xing Wu; Hao Shi; Bojie Fu; Ting Li; Yihe Lü; Lingfan Wan; Shuang Zhang; Binbin Huang; Yibin Shi (Agriculture, Ecosystems & Environment, 2025)

Improving urban butterfly diversity and abundance through strategic consideration of patch resources and butterfly ecological preference - Wenqiang Fang; Weicong Fu; Zihao Chen; Peilin Huang; Shaolin Peng; Ting Zhou (Urban Forestry & Urban Greening, 2025)

Microplastics: an overlooked particle organic carbon in river systems - Xuke Liu; Weijian Zhou; Peng Cheng; Fei Zhang; Liangcheng Tan; Yunchong Fu; Yukun Fan; Jianghu Lan; Huachun Gu; Wen Liu; Ting Wang (Science Bulletin, 2025)

Multi-trophic communities in river ecosystems: Insights into environmental drivers and assembly mechanisms for ecological management— a case study in the Minjiang River - Yu Xiang; Liwei Fu; Ting Cai; Han Zhang; Wenliang Xiang; Ruxin Yang; Mengli Chen (Environmental Research, 2025)

Enhanced piezo-Fenton synergies enabled by interface-engineered 0D/3D heterojunctions (Fe2O3 QDs@BTO): investigation of interfacial behavior and reaction mechanism - Shuai Liu; Xueyao Wang; Xuyang Hu; Lihui Huang; Ting Sun; Lingshuai Kong; Zhenhui Gao; Rongbing Fu; Yu Xiao (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Editorial Expression of Concern: The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2025)

The novel model INEDM and two traditional models for estimating the carrying capacity of Hong Kong oyster (Crassostrea hongkongensis) in two aquaculture systems in Guangdong Province of China - Xing-Chi Guo; Wen-Ding Liu; Xiao-Yan Ye; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2025)

UV-guided separation of polyacetylenol glycosides from the edible roots of Codonopsis pilosula and their anti-inflammatory activity - Xilan Jiang; Lun Wang; Yao Chen; Yi Zuo; Mengdan Liu; Bin Chen; Dong Fu; Yujiao He; Mingkui Wang; Ting Shen; Fu Li (Phytochemistry, 2025)

Resilience-oriented road network recovery strategies with urban air mobility under rainstorm-induced waterlogging - Luyao Wang; Jianjun Wu; Xin Yang; Hao Fu; Shuang Yang; Ting Wang (Journal of Transport Geography, 2025)

Investigation of wind load characteristics and structural responses in asymmetric linked twin-tower high-rise buildings - Yangxue Wang; Ting Deng; Jiyang Fu (Engineering Structures, 2025)

A synergistic antifungal strategy using multifunctional nanoplatform for vaginitis therapy - Jinjie Hou; Ruijie Fu; Ting Yu; Yunlei Xianyu (Chemical Engineering Journal, 2025)

Ag nanoparticles anchored on oxygen vacancy-rich alumina catalyst for efficient bacterial inactivation - Ting Wang; Fangyuan Gu; Leyang Xu; Wenqi Tang; Yanfeng Han; Yongjie Wang; Shi Yang; Weiying Wang; Xinlong Zhang; Tianshuo Zhao; Biao Ran; Chaopeng Fu; et al. (Chemical Engineering Journal, 2025)

Waterworks sludge coupled with biochar and pyrite as wetland substrates for enhanced nitrogen removal and greenhouse gases mitigation: First study on synergistic mechanisms - Yujie Yuan; Yaqian Zhao; Tao Zhang; Ting Wei; Yamei Cai; Lei Yang; Jingmiao Fu; Ang Liu; Anran Yang (Chemical Engineering Journal, 2025)

Reduced Usage of GLS Intronic Polyadenylation Promotes Cellular Senescence - Xueping Li; Yuxin Li; Dong Ding; Baiyun Xie; Jun Yao; Yu Chen; Zhaozhao Zhao; Peng Yu; Shengwei Zhang; Fu Yang; Ting Ni; Gang Wei (Phenomics, 2025)

Immune responses of Ctenopharyngodon idella juveniles against the ciliated parasite's reinfection induced by Ichthyophthirius multifiliis theronts at the threshold density - Ting-Long Hou; Yao-Wu Fu; Xing-Chi Guo; Shu-Guan Guo; Shi-Lu Huang; Qi-Zhong Zhang (Aquaculture, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Lanthanum-based hydrogels for simultaneous removal of trace phosphorus and algae - Yan Zhang; Qian Xie; Cheng Fu; Zhen Qiu; Zechao Zhuang; Ting Wang; Yunying Fang; Yongfu Li; Yanjiang Cai; Huajun Feng; Bing Yu (Chemical Engineering Journal, 2025)

A saline lacustrine depositional environment enhances organic matter enrichment in the Permian Lucaogou shales - Yin Fu; Zuodong Wang; Ting Zhang; Wenjun Wang; Yongli Wang; Wang Zhang; Xiaobin Li; Zhiyong Wang (Organic Geochemistry, 2025)

Antibacterial mechanism of lysine against Escherichia coli O157:H7, its action on lettuce and in reducing the severity of murine colitis - Lei Tian; Luyao Ma; Yudong Tian; Ting Zhou; Chunling Zhang; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; Xin Wang (Food Microbiology, 2025)

A novel hybrid machine learning approach for accurate retrieval of ocean surface chlorophyll-a across oligotrophic to eutrophic waters - Ting Qin; Tianlong Liang; Donglin Fan; Hongchang He; Guiwen Lan; Bolin Fu (Environmental Research, 2025)

Continuous reduction in socio-ecological system vulnerability on the Qinghai–Tibet Plateau from 2000 to 2050 under an intermediate protection scenario - Zhengyuan Zhao; Bojie Fu; Yihe Lü; Ting Li; Yuelu Wang; Haoyue Wang; Binbin Huang; Xing Wu (Environmental Impact Assessment Review, 2025)

Valorization of solid digestate through biochar production for toluene adsorption and enhanced energy recovery as solid recovered fuel - Shao-Fu Tu; Yu-Ming Chu; Tse-Lun Chen; Hsing-Cheng Hsi; Hwong-wen Ma; Yu-Chieh Ting (Waste Management, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Mold severity and fungal communities in university dormitories: The role of building characteristics and living habits - Qiujia Lai; Ting Fu; Di Huang; Shan Gao; Huan Liu; Ana Sofia Guimarães; Chi Feng (Building and Environment, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

The significance of organophosphate flame retardants in patients with esophageal squamous cell carcinoma - Hung-I Lu; Wan-Ting Huang; Wen-Chin Lee; Fu-Jen Cheng; Chia-Te Kung; Chin-Chou Wang; Liang-Jen Wang; Yu-Che Ou; Shau-Hsuan Li (Environmental Geochemistry and Health, 2025)

Discovery of structurally intriguing diterpenoids as anti-neuroinflammatory agents from mangrove plant Excoecaria agallocha L. via inhibiting macrophage polarization and inflammasome - Jun-Yi Li; Ming-Bin Chen; Ting-Ting Fu; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Jing Zhou; Yong Rao; Zhong-Ping Jiang; Ling Huang (Phytochemistry, 2025)

Controlling the morphology of CdS deposited on nickel foam for concurrent 4-nitrophenol reduction and electricity generation - Ting Du; Zelong Zheng; Lihang Ma; Yanyang Xu; Xiaobin Liao; Baoling Yuan; Ming-Lai Fu; Yi-bo Hu (Journal of Environmental Chemical Engineering, 2025)

Comprehensive evaluation of surface water in the Qujiang River Basin through a newly proposed water quality index combined with positive matrix factorization and hazard quotient/index model - Dong Fu; Xinruo Wang; Yanchuan Gong; Hua Liu; Ting Long; Lvshan Zhou; Chuntan Chen; Hanyi Liu (Journal of Environmental Chemical Engineering, 2025)

Arginine-terminated egg white peptide Leu-Phe-Arg (LFR) repairs intestinal barrier damage through the PI3K/AKT/mTOR/p70s6k signaling pathway: An analysis combined transcriptomics and proteomics - Siwen Lyu; Menghan Fu; Qi Yang; Qingwen Han; Shengrao Li; Yingnan Zeng; Jingbo Liu; Yiding Yu; Ting Zhang (Food Bioscience, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Photothermal-magnetic driven post-targeting retention and cascade therapy of “biomimetic glue”-based nanoreactor for cancer theranostics by bystander-like killing - Zihan Liu; Ting Yang; Jiale Miao; Weiqing Ni; Zixuan Fu; Jing Hei; Jiayu Yang; Yanhua Liu (Chemical Engineering Journal, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

An EXPAR-CRISPR/Cas12a Assay for Rapid Detection of Salmonella - Wensen Lin; Mintao Huang; Hongjian Fu; Luxin Yu; Ying Chen; Lingwei Chen; Yanzhen Lin; Ting Wen; Xiaomin Luo; Yanguang Cong (Current Microbiology, 2025)

Crab species recognition method based on incremental learning - Duan Qingling; Feng Xiaoxiao; Kong Mingrui; Fu Jiayi; Zhang Ting (Aquaculture International, 2025)

PRDX1 affects acrylamide-induced neural damage through the PTEN/AKT signaling pathway - Dong-Xue Fu; Ya-Ting Lei; Hai-Bo Guo; Ting Chen; Xiang-Ying Gao; Xiao-Li Wang; Xiang Huang; Ling-Ling Song; Sheng-Yuan Wang; Qin-Xue Dai (NeuroToxicology, 2025)

Long-term study of Citrus changshan-huyou Y.B. Chang essential oil: Chemical transformations and their impact on antibacterial efficacy - Wenbin Xiao; Jiajing Guo; Yanjiao Fu; Zixuan Li; Tongping Zhang; Mingwang He; Ting Liu; Yangbo Xiao; Xuebo Shang; Fuhua Fu; Gaoyang Li; Donglin Su; et al. (Food Chemistry, 2025)

Bayesian operational modal analysis of two supertall buildings under Super Typhoon Saola - Haoran Pan; Fan Jiang; Jiurong Wu; Ting Deng; Jiyang Fu (Engineering Structures, 2025)

Arsenic Accumulation in Different Parent Materials of Rice (Oryza Sative L.) are Affected by Root Morphology - Yi Chen; Dehui Tu; Deqiang Li; Yinggang Xu; Yueyi Wu; Zhaoyong Zeng; Xiaoyan Tang; Yang Li; Chaorui Yan; Ting Lan; Fu Huang; Xuesong Gao; et al. (Journal of Plant Growth Regulation, 2025)

Magnolin ameliorates acetaminophen-induced liver injury in mice via modulating the MAPK pathway and lipid metabolism - Ting Yao; Youhe Wu; Liyun Fu; Lanjun Li (Toxicology and Applied Pharmacology, 2025)

New pathway under light: conversion of furans to pyrroles - Yue-Liu-Ting Fu; Jun-Wei Shi; Peng Chen; Wen-Jing Xiao; Liang-Qiu Lu (Science Bulletin, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

Elevated hemoglobin adducts derived from crotonaldehyde in healthy smokers and oral cancer patients by nanoflow liquid chromatography tandem mass spectrometry☆ - Kai-Ting Fu; Deng-Chyang Wu; Hauh-Jyun Candy Chen (Chemico-Biological Interactions, 2025)

Surface display of aspartate ammonia-lyase from Lactobacillus paracasei on Pichia pastoris - Chen-Chi Chang; Yi-Hao Huang; Hua-Kun Fu; Kai-Wei Chang; Shih-Hsuan Chen; Yu-Ting Yu; Xin-Ying Lau; Jhih-Ying Ciou; He-Yuan Hsieh; Yung-Ju Chen; Lu-Sheng Hsieh (World Journal of Microbiology and Biotechnology, 2025)

Winter wheat harvest detection via Sentinel-2 MSI images - Jibo Yue; Yihan Yao; Jianing Shen; Ting Li; Nianxu Xu; Haikuan Feng; Yihao Wei; Xin Xu; Yinghao Lin; Wei Guo; Yuanyuan Fu; Hongbo Qiao; et al. (International Journal of Remote Sensing, 2025)

Responses of zebrafish to chronic environmental stressors: anxiety-like behavior and its persistence - Xiao-hong Li; Cheng Fu; Xue-ting Tan; Shi-jian Fu (Frontiers in Marine Science, 2025)
Introduction Fish in natural ecosystems face long-term environmental stressors, with anxiety being a critical stress response. This study investigates how chronic stressors—predators, social isolation, and caffeine—affect anxiety-like behavior and cortisol levels in zebrafish ( Danio rerio ), and examines the persistence of these effects post-stressor removal. Methods Zebrafish were exposed to three stressors for 14 days. Anxiety-like behavior and cortisol levels were measured for up to 28 days following the removal of the stressors. Results Chronic predator stress significantly increased anxiety-like behavior and cortisol levels, persisting for at least seven days post-removal. Social isolation reduced anxiety-like behavior and cortisol levels, with effects lasting no less than one day after re-socialization. Caffeine induced temporary anxiolytic effects, reversing one day post-withdrawal and persisting for at least seven days, while cortisol levels remained elevated. Discussion Zebrafish exhibit stressor-specific behavioral and physiological changes with varying persistence. These findings enhance understanding of fish responses to environmental stressors, offering insights into their survival strategies and ecosystem health.

The application of pressure-driven ceramic-based membrane for the treatment of saline wastewater and desalination–A review - Yuehua Zhang; Ting Chen; Xianfu Chen; Kaiyun Fu; Minghui Qiu; Yiqun Fan (Desalination, 2025)

Deciphering direct and indirect factors contributing to airborne microbes in university dormitories - Lumeng Liu; Di Huang; Shuwan Wang; Qisheng Li; Ting Fu; Qiujia Lai; Chi Feng; Meng Liu; Huan Liu (Building and Environment, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Sublethal effects of lambda-cyhalothrin on the biological characteristics, detoxification enzymes, and genes of the papaya mealybug, Paracoccus marginatus - Jian-Yu Li; Yan-Ting Chen; Yan Chen; Jian-Wei Zhao; Jian-Wei Fu; Meng-Zhu Shi (Journal of Pest Science, 2025)

Acute caffeine supplementation offsets the impairment in 10-km running performance following one night of partial sleep deprivation: a randomized controlled crossover trial - Yi-Shan Tsai; Ting-Tzu Chen; Yau-Ching Chan; Chun-Chin Huang; Ting-Fu Lai; Yung Liao; Richard S. Metcalfe; Yung-Chih Chen; Ho-Seng Wang (European Journal of Applied Physiology, 2025)

Rhizosphere bacterial communities mediate the effect of maize-soybean strip intercropping and nitrogen management on cadmium phytoextraction - Yuze Li; Ting Xing; Zhidan Fu; Tian Pu; Peng Ding; Yushan Wu; Feng Yang; Xiaochun Wang; Taiwen Yong; Wenyu Yang (Applied Soil Ecology, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

Establishment and application of TaqMan probe-based quantitative real-time PCR for rapid detection and quantification of Ichthyophthirius multifiliis in farming environments and fish tissues - Shu-Quan Guo; Yao-Wu Fu; Ting-Long Hou; Shi-Lu Huang; Qi-Zhong Zhang (Veterinary Parasitology, 2025)

Optimizing pedestrian thermal comfort in urban street canyons for summer and winter: Tree planting or low-albedo pavements? - Tailong Zhang; Xiaotong Fu; Feng Qi; Yamei Shen; Peng Xu; Yizhou Tao; Ting Liu; Yukai Song (Sustainable Cities and Society, 2025)

Temporal variations of N and P losses via surface runoff from Chinese farmland after fertilisation - Luoqi Zhao; Denggao Fu; Ting Li; Xinqi Yuan; Sichen Wang; Change Liu; Changqun Duan (Soil and Tillage Research, 2025)

Coal dust combustion suppression via melamine polyphosphate and silica: Experiment and simulation - Shuang Geng; Ting Zhang; Xin Zhang; Shaoqian Cheng; Guoen Fu; Jianfu Xu; Wen Zhou; Yanhua Lan; Xueqiang Shi; Chi-Min Shu; Weiguo Cao (Fuel, 2025)

Directional anchoring of polymer-lysozyme nanohybrids for adhesive capture and enhanced removal of Alicyclobacillus acidoterrestris in fruit juices - Bingzhi Li; Kun Cheng; Lunjie Huang; Pengyu Chen; Linpin Luo; Liang Zhang; Ting Du; Tong Zhang; Qingqing Li; Yiyue Ma; Bangfeng Fu; Maojun Jin; et al. (Food Chemistry, 2025)

A case study from a critical stopover site in the East Asian-Australasian Flyway provides lessons for optimal high-tide roost management to support shorebird conservation - Jia Guo; Waner Liang; Yan Zhou; Yifei Jia; Hongyan Yang; Lili Sun; Qing Chen; Ting Fu; Sicheng Ren; Wenkui Jiang; Guangchun Lei; Li Wen (Biological Conservation, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Modified water-retention model containing a swelling-shrinkage variation feature: Investigation attapulgite-treated soil permeability - Ting Yang; Wei Fu (Bulletin of Engineering Geology and the Environment, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

Effects of slurry ice treatment on the physicochemical changes and proteome of large yellow croaker (Larimichthys crocea) - Yan-wei Yuan; Yu-ting Liu; Xing-tong Zhu; Jin-xiu Yu; Jun-long Mao; Jing-jing Fu; Yue-wen Chen; Guo-feng Tan (Food Chemistry, 2025)

Confirmation of pro-wound healing egg white peptides LVEEY and QVPLW and analysis of their mechanism of action: A proteomic analysis - Ting Zhang; Menghan Fu; Qi Yang; Feng Jiang; Shengrao Li; Zhiyang Du; Xuanting Liu; Jingbo Liu; Siwen Lyu (Food Bioscience, 2025)

Transition metal doped MoS2 for piezoelectric Fenton-catalyzed degradation of norfloxacin: Rapid innergenerated-H2O2 conversion and dual pathways of non-radicals and radicals - Xueyao Wang; Shuai Liu; Lihui Huang; Ting Sun; Lingshuai Kong; Zhenhui Gao; Rongbing Fu; Yu Xiao (Chemical Engineering Journal, 2025)

In-situ packing self-intumescent aerogel particles in rigid polyurethane foam towards thermal insulation, flame retardance and smoke suppression - Ning Yu; Ting Wang; Cheng-Xu Xu; Xue Gou; Ying-Jiao Zhan; Wenli An; Zhi-Cheng Fu; Jinni Deng; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Selective Activation of G Protein–Coupled Estrogen Receptor 1 (GPER1) Reduces ER Stress and Pyroptosis via AMPK Signaling Pathway in Experimental Subarachnoid Hemorrhage - Yidan Liang; Wenqiao Fu; Yin Tang; Hongjiang Ye; Yanglingxi Wang; Chao Sun; Yi Xiang; Weiming Xiong; Min Cui; Yuanlin Chen; Ting Wang; Yongbing Deng (Molecular Neurobiology, 2025)

The role of deep learning in aortic aneurysm segmentation and detection from CT scans: A systematic review and meta-analysis - Ting-Wei Wang; Yun-Hsuan Tzeng; Jia-Sheng Hong; Ho-Ren Liu; Hao-Neng Fu; Yung-Tsai Lee; Wei-Hsian Yin; Yu-Te Wu (Next Research, 2024)

A comprehensive study of catalytic pyrolysis of antibiotic fermentation residue over red mud-Ca(OH)2 composites - Xiaomin Cui; Zhaojia Ting; Jiawen Fu; Suthajini Thiruketheeswaranathan; Weiguo Dong; Ming Zhao (Journal of Hazardous Materials, 2024)

Improvement of soil nutrient cycling by dominant plants in natural restoration of heavy metal polluted areas - Ting Li; Sichen Wang; Luoqi Zhao; Xinqi Yuan; Yuhan Gao; Denggao Fu; Chang'e Liu; Changqun Duan (Environmental Research, 2024)

MBSFC: hyperspectral image classification based on multi-branch and spectral feature conversion - Ting Tang; Shaopeng Liu; Xueliang Fu; Weihong Yan; Xiaoling Luo; Xin Pan (International Journal of Remote Sensing, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Six element high-entropy Prussian blue analogue cathode enabling high cycle stability for sodium-ion batteries - Zhe Qian; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Xuan Xu; Zhe Mei; Zi-Ting Zhou; Zheng-Wen Fu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Enhanced control and efficiency in millimeter-scale composite droplets preparation - Jijie Fu; Kai Mu; Fangsheng Huang; Zhiqiang Zhu; Ting Si (Chemical Engineering Journal, 2024)

Micro/nano system-mediated local treatment in conjunction with immune checkpoint inhibitor against advanced-Stage malignant melanoma - Lu Tang; Hening Liu; Yue Yin; Ting Pan; Cong Fu; Yuqi Cao; Yijun Mei; Qiaqia Xiao; Ziwei Yan; Yi Yao; Haijuan Dong; Wei Wang (Chemical Engineering Journal, 2024)

Long-term green manuring increases soil carbon sequestration via decreasing qCO2 caused by lower microbial phosphorus limitation in a dry land field - Zhengbo Ma; Ting Liang; Haoran Fu; Qingxu Ma; Danna Chang; Jiudong Zhang; Zongxian Che; Guopeng Zhou; Weidong Cao (Agriculture, Ecosystems & Environment, 2024)

Novel findings on the mitochondria in ciliates, with description of mitochondrial genomes of six representatives - Tengteng Zhang; Jinyu Fu; Chao Li; Ruitao Gong; Khaled A. S. Al-Rasheid; Naomi A. Stover; Chen Shao; Ting Cheng (Marine Life Science & Technology, 2024)
Determining and comparing mitochondrial genomes (mitogenomes) are essential for assessing the diversity and evolution of mitochondria. Ciliates are ancient and diverse unicellular eukaryotes, and thus are ideal models for elucidating the early evolution of mitochondria. Here, we report on six new mitogenomes of spirotrichs, a dominant ciliate group, and perform comparative analyses on 12 representative species. We show that: (1) the mitogenomes of spirotrichs are linear structures with high A+T contents (61.12–81.16%), bidirectional transcription, and extensive synteny (except for the nad5 , ccmf and cob genes in Euplotia); (2) the non-split of NADH dehydrogenase subunit 2 gene ( nad2 ) is a plesiomorphy of ciliates, whereas it has evolved into a split gene in Spirotrichea (apart from Euplotes taxa), Oligohymenophorea, and Armophorea; (3) the number of small subunit ribosomal proteins (rps) encoded in mitogenomes increases in the later branching classes of ciliates, whereas rps8 shows a loss trend during the evolution of Euplotes taxa; (4) the mitogenomes of spirotrichs exhibit A/T codon bias at the third position, and the codon bias is mainly due to DNA mutation in oligotrichs, hypotrichs and Diophrys appendiculata ; (5) the phylogenetic position of D. appendiculata is unstable and controversial based on both phylogenetic analyses and mitogenome evidence. In summary, we investigated the mitogenome diversity of spirotrichs and broadened our understanding of the evolution of mitochondria in ciliates.

Emission characteristic, spatial distribution, and health risk of polycyclic aromatic compounds (PAHs, NPAHs, and OPAHs) from light-duty gasoline and diesel vehicles based on on-road measurements - Jiaqi Fu; Tiange Fang; Yutong Gao; Ting Wang; Zhenyu Jia; Dongping Guo; Hongjun Mao (Science of The Total Environment, 2024)

Fruits’ cold tolerance: a review of mechanisms and methods - Jian-Lin He; Gang-Shuai Liu; Xiao-Dan Zhao; Lan-Ting Xiang; Shi-Yin Xie; Yun-Xiang Wang; Da-Qi Fu (Postharvest Biology and Technology, 2024)

The impact of China certified emission reduction market resumption on manufacturers' stock market valuations: The role of OSCM factors - Fu Jia; Ting Pan; Qin He; Lujie Chen (Journal of Cleaner Production, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Combined use of chemical dust suppressant and herbaceous plants for tailings dust control - Yonghao Yang; Zhihao Luo; Zuoan Wei; Junkang Zhao; Ting Lu; Tianbao Fu; Shuang Tang (Environmental Geochemistry and Health, 2024)

Ultrasound probe enhanced enzymatic hydrolysis for rapid separation of β2-adrenergic agonists from animal urine and livestock wastewater: Applicability to biomonitoring investigation - Zhiming Xiao; Yinji Jin; Ying Cao; Ting Yao; Yao Fu; Decheng Suo; Shi Wang; Gang Chen; Xinxue Zhao; Runxian Li; Xia Fan (Analytica Chimica Acta, 2024)

Multi-dimensional microfluidic paper-based analytical devices (μPADs) for noninvasive testing: A review of structural design and applications - Ting Chen; Ce Sun; Syed Comail Abbas; Nur Alam; Sheng Qiang; Xiuzhi Tian; Chenglong Fu; Hui Zhang; Yuanyuan Xia; Liu Liu; Yonghao Ni; Xue Jiang (Analytica Chimica Acta, 2024)

Activation of GPR30 Ameliorates Cerebral Ischemia–Reperfusion Injury by Suppressing Ferroptosis Through Nrf2/GPX4 Signaling Pathway - Yong-qiang Zhang; Ting Sun; Zhen Zhao; Jing Fu; Le Yang; Yuan Xu; Jing-feng Zhao; Xiu-ling Tang; An Liu; Ming-gao Zhao (NeuroMolecular Medicine, 2024)

Interaction of rice root Fe plaque with radial oxygen loss enhances paddy-soil N2O emission by increasing •OH production and subsequently inhibiting N2O reduction - Jinzhi Yao; Yingdong Fu; Zhuyun Yu; Ting Liu; Tim J. Clough; Chunsheng Hu; Shuping Qin (Soil Biology and Biochemistry, 2024)

Garciyunnanones A–R: Caged polycyclic polyprenylated acylphloroglucinols decorated with a lavandulyl substituent from Garcinia yunnanensis - Miaomiao Nan; Yueyou Yang; Ping Ying; Qiang Zheng; Youjun Wu; Tianjie Cao; Ting Li; Weiming Huang; Chuanlu Fu; Lingyi Kong; Wenjun Xu (Phytochemistry, 2024)

Synergistic mechanism and toxicity reduction potential in medium-pressure UV/chlorine/TiO2 system for metronidazole removal - Yu-qiong Gao; Xiang-mei Zhong; Xue-ting Ren; Fu-xiang Tian; Nai-yun Gao; Cong Li (Journal of Water Process Engineering, 2024)

The role of a novel secretory peptidoglycan recognition protein with antibacterial ability from the Chinese Oak Silkworm Antheraea pernyi in humoral immunity - Xutong Duan; Ting Fu; Chang Liu; Fuhui Wang; Chengbao Liu; Lin Zhao; JinZhu Yu; Xialu Wang; Rong Zhang (Insect Biochemistry and Molecular Biology, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Study on Warning Method for Fault Rockburst in Deep TBM Tunnels - Yu Zhang; Xia-Ting Feng; Zhibin Yao; Wei Zhang; Lei Hu; Chengxiang Yang; Yongrun Xiong; Lianjie Fu (Rock Mechanics and Rock Engineering, 2024)

Effects of Various Depressurization Paths on Desorption Deformation and Gas Production of Medium-Rank Coal in Qinshui Basin - Ming Cheng; Xuehai Fu; Junqiang Kang; Ting Liu; Jielin Lu (Natural Resources Research, 2024)

Deep Learning Models for Aorta Segmentation in Computed Tomography Images: A Systematic Review And Meta-Analysis - Ting-Wei Wang; Yun-Hsuan Tzeng; Jia-Sheng Hong; Ho-Ren Liu; Kuan-Ting Wu; Hao-Neng Fu; Yung-Tsai Lee; Wei-Hsian Yin; Yu-Te Wu (Journal of Medical and Biological Engineering, 2024)
Purpose This systematic review and meta-analysis was conducted to evaluate the usefulness of deep learning (DL) models for aorta segmentation in computed tomography (CT) images. Methods Adhering to 2020 PRISMA guidelines, we systematically searched PubMed, Embase, and Web of Science for studies published up to March 13, 2024, that used DL models for aorta segmentation in adults’ chest CT images. We excluded studies that did not use DL models, involved nonhuman subjects or aortic diseases (aneurysms and dissections), or lacked essential data for meta-analysis. Segmentation performance was evaluated primarily in terms of Dice scores. Subgroup analyses were performed to identify variations related to geographical location and methodology. Results Our review of 16 studies indicated that DL models achieve high segmentation accuracy, with a pooled Dice score of 96%. We further noted geographical variations in model performance but no significant publication bias, according to the Egger test. Conclusion DL models facilitate aorta segmentation in CT images, and they can therefore guide accurate, efficient, and standardized diagnosis and treatment planning for cardiovascular diseases. Future studies should address the current challenges to enhance model generalizability and evaluate clinical benefits and thus expand the application of DL models in clinical practice.

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Rapid visual detection of sulfur dioxide residues in food using acid-sensitive CdTe quantum dots-loaded alginate hydrogel beads - Wei Lan; Yanmin Rao; Xiangyu Zhao; Yi Zhao; Xinyi Min; Yue Wu; Ziyi Jiang; Ting Li; Yinhua Li; Hengye Chen; Wanjun Long; Yuanbin She; et al. (Food Chemistry, 2024)

“Edge in-situ heterogeneous” BiOI based on defect engineering and non-noble metal deposition: Boosting visible-light photocatalytic sterilization - Bangfeng Fu; Yifan Pan; Peng Zhao; Liang Zhang; Junchen Zhuo; Jianxing Feng; Bingzhi Li; Lenan Yao; Jiafeng Xi; Xi Lan; Linpin Luo; Ting Du; et al. (Chemical Engineering Journal, 2024)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

Comparison of the osteogenic potential of fibroblasts from different sources - Jiaojiao Li; Liangliang Fu; Qian Lu; Shuling Guo; Si Chen; Ting Xia; Min Wang; Liangwen Chen; Yi Bai; Haibin Xia (Tissue and Cell, 2024)

Variable climatic conditions dominate decreased wetland vulnerability on the Qinghai‒Tibet Plateau: Insights from the ecosystem pattern-process-function framework - Zhengyuan Zhao; Bojie Fu; Yihe Lü; Ting Li; Lei Deng; Yuelu Wang; Da Lü; Yi Wang; Xing Wu (Journal of Cleaner Production, 2024)

Mechanism of radial chain rockbursts in a deep granite TBM tunnel under the influence of weak band - Lianjie Fu; Xia-Ting Feng; Zhibin Yao; Wei Zhang; Lei Hu; Yu Zhang; Yongrun Xiong (Engineering Geology, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Pilot-scale membrane-covered composting of food waste: Initial moisture, mature compost addition, aeration time and rate - Fei Wang; Ting Pan; Dafang Fu; Ioannis A. Fotidis; Christina Moulogianni; Yixin Yan; Rajendra Prasad Singh (Science of The Total Environment, 2024)

Mechanism of zinc stress on magnesium deficiency in rice plants (Oryza sativa L.): Insights from magnesium isotopes - Yucong Fu; Ting Gao; Qiqi Wu; Meng Qi; Zhengrong Wang; Chengshuai Liu (Science of The Total Environment, 2024)

Insight into energy release characteristics of TiH2 dust explosion through ignition experiments and molecular dynamic simulations - Ting Zhang; Jiefan Zhang; Shuang Geng; Xin Zhang; Runqing Liu; Guoen Fu; Jianfu Xu; Haixia Zhao; Yanhua Lan; Yongan Feng; Weiguo Cao (Process Safety and Environmental Protection, 2024)

Lemon essential oil nanoemulsions: Potential natural inhibitors against Escherichia coli - Wenbin Xiao; Zhipeng Gao; Ting Liu; Weiming Zhong; Sifan Jiang; Mingwang He; Fuhua Fu; Gaoyang Li; Donglin Su; Jiajing Guo; Yang Shan (Food Microbiology, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Outer membrane vesicles of avian pathogenic Escherichia coli induce necroptosis and NF-κB activation in chicken macrophages via RIPK1 mediation - Zhe Li; Wenbin Shang; Ting Mei; Dandan Fu; Feng Xi; Ying Shao; Xiangjun Song; Zhenyu Wang; Kezong Qi; Jian Tu (Research in Veterinary Science, 2024)

Cadmium disrupts spermatogenic cell cycle via piRNA-DQ717867/p53 pathway - Jiaoyang Wei; Juan Dai; Xiaofan Shi; Ruixue Zhao; Guoqing Fu; Rui Li; Chao Xia; Ling Zhang; Ting Zhou; Huaiji Wang; Yuqin Shi (Reproductive Toxicology, 2024)

Heat storage and release characteristics of a prototype CaCO3/CaO thermochemical energy storage system based on a novel fluidized bed solar reactor - Fuliang Nie; Tianzeng Ma; Qiangqiang Zhang; Zheshao Chang; Ting Ren; Khurshida F. Sayfieva; Mingkai Fu; Xin Li (Journal of Cleaner Production, 2024)

Dual purpose ratooned rice improves agri-food production with reduced environmental cost - Deqiang Qi; Ke Liu; Mingfang Fu; Matthew Tom Harrison; Xiaofei Shi; Xiangchen Liu; Peter de Voil; Yunbo Zhang; Ando Radanielson; Wenge Wu; Jingrui Chen; Yu Jiang; et al. (Journal of Cleaner Production, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Stem Cell-Based Strategies: The Future Direction of Bioartificial Liver Development - Lei Feng; Yi Wang; Yu Fu; Ting Li; Guolin He (Stem Cell Reviews and Reports, 2024)

Spatially-assembled binary carbon anode synergizing directional electron transfer and enriched microbe accommodation for wastewater treatment and energy conversion: From simulation to experiments - Mengxi Yin; Boya Fu; Ting Xu; Xiaoxin Cao; Xia Huang; Xiaoyuan Zhang (Water Research, 2024)

Soil freeze–thaw cycles affect spring phenology by changing phenological sensitivity in the Northern Hemisphere - Ting Li; Bojie Fu; Yihe Lü; Chenjun Du; Zhengyuan Zhao; Fangfang Wang; Guangyao Gao; Xing Wu (Science of The Total Environment, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

T-2 toxin induces mitochondrial dysfunction in chondrocytes via the p53-cyclophilin D pathway - Fang-fang Yu; Shui-yuan Yu; Lei Sun; Juan Zuo; Kang-ting Luo; Miao Wang; Xiao-li Fu; Feng Zhang; Hui Huang; Guo-yu Zhou; Yan-jie Wang; Yue Ba (Journal of Hazardous Materials, 2024)

Wilson cycles of the Zagros fold and thrust belt: A comprehensive review - Xiaofei Fu; Zhiqiang Feng; Faqiang Zhang; Zhongmin Zhang; Jinrui Guo; Zhe Cao; Ting Kor; Ming Cheng; Jianzhao Yan; Yu Zhou (Journal of Asian Earth Sciences, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Construction of defective hydroxyl-rich metal–organic framework for effective capture of borate ion - Ting Wang; Jia Fu; Weidong Zhang; Dahuan Liu (Chemical Engineering Journal, 2024)

A novel process for efficient utilization of bamboo fiber resource in dissolving pulp production by fiber fractionation: Laboratory study and mill trials - Yishan Liu; Chenglong Fu; Lianli Liu; Ke Wang; Ting Wu; Jingjing Wu; Junmiao Zhang; Zhanghong Xie; Yinchuan Xu; Chao Duan; Yonghao Ni; Zhibin He (Bioresource Technology, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Identification and characterization of β3 integrin in Crassostrea hongkongensis - Lei Tang; Shu-Quan Guo; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2024)

Thermal degradation kinetics of cynatratoside-C and its antiparasitic efficacy after being stored in sterile water and aquaculture water - Shi-Lu Huang; Shu-Quan Guo; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2024)

Pathogen-induced methylglyoxal negatively regulates rice bacterial blight resistance by inhibiting OsCDR1 protease activity - Zheng-Wei Fu; Jian-Hui Li; Xiang Gao; Shi-Jia Wang; Ting-Ting Yuan; Ying-Tang Lu (Molecular Plant, 2024)

Enhanced removal of sulfamethoxazole by Mn(II)/bisulfite in presence of nitrilotriacetic acid: Role of Mn(III) - Yiqing Liu; Ting Wang; Zhengjie Chen; Shenglan Liu; Yongsheng Fu (Journal of Environmental Chemical Engineering, 2024)

Sulfhydryl-mediated etching suppression of gold nanostars for rapid and sensitive detection of bacterial pathogens - Ting Yu; Ying Fu; Jiuhong Yi; Zexiang Wang; Jun Zhang; Yunlei Xianyu (Chemical Engineering Journal, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Triple physical cross-linking cellulose nanofibers-based poly(ionic liquid) hydrogel as wearable multifunctional sensors - Dong Fu; Yang Xie; Lili Zhou; Lili Zhang; Ting Zheng; Jun Shen (Carbohydrate Polymers, 2024)

Exploitation of function groups in cellulose materials for lithium-ion batteries applications - Yuanyuan Xia; Xinping Li; Jingshun Zhuang; Wenliang Wang; Syed Comail Abbas; Chenglong Fu; Hui Zhang; Ting Chen; Yue Yuan; Xingjin Zhao; Yonghao Ni (Carbohydrate Polymers, 2024)

Hydrogen sulfide promoted cell differentiation, antioxidant ability, and flavonoids accumulation in Ginkgo biloba L. suspension cells - Jin-ling Lu; Yu-chen Hu; Ying Chen; Rui Liu; Jing-jing Di; Ting-ting Feng; Fu-liang Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Overlooked encounter process that affects physical behaviors of stabilized nanoscale zero-valent iron during in situ groundwater remediation - Yujie Xie; Miaoyue Zhang; Lihang Ma; Ting Du; Dan Zhou; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Journal of Hazardous Materials, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Ionospheric response characteristics and PPP accuracy analysis at different latitudes during strong geomagnetic storms - Dongjie Chen; Zhenluan Hu; Fu Wang; Yanmei Gou; Ting Zhang (Acta Geophysica, 2023)

Cultivation and biogeochemical analyses reveal insights into biomineralization caused by piezotolerant iron-reducing bacteria from petroleum reservoirs and their application in MEOR - Hao Dong; Li Yu; Ting Xu; Yulong Liu; Jian Fu; Yanlong He; Ji Gao; Jiaqi Wang; Shanshan Sun; Yuehui She; Fan Zhang (Science of The Total Environment, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

The roles of Methylobacterium organophilum and Sphingomonas melonis for accelerating N-methyl pyrrolidone (NMP) biodegradation - Yongyi Gao; Ting Chen; Yifan Hou; Ruiyun Xue; Rui Liu; Fu Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Water Process Engineering, 2023)

Human dental pulp stem cells have comparable abilities to umbilical cord mesenchymal stem/stromal cells in regulating inflammation and ameliorating hepatic fibrosis - Peixing Chen; Yanchun Lin; Wenbo Lin; Yun Li; Ting Fu; Yuanyue Liu; Tian Guan; Man Xin; Ling Ye; Peiluan Wang; Haoyu Zeng; Kaitao Yao (Human Cell, 2023)

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Lanostane triterpenoids with anti-proliferative and PTP1B/α-glucosidase inhibitory activities from the fruiting bodies of Ganoderma calidophilum - Li Yang; Ting-Ting Zhang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; Zhi-Fang Yu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2023)

Topsoil selenium (Se) under Se-rich farming in China: Current status, cropping impacts and ecological risk assessment - Li Qian; Ting Wang; Yajuan Shi; Qiuyun Xu; Xuan Zhou; Lingjie Ke; Ruoyu Liang; Chuancheng Fu; Xiaoqi Zheng; Guoxin Sun (Journal of Environmental Management, 2023)

Evolution law and mechanism of time-delayed spalling in a deep TBM tunnel: A case study - Chen Fan; Xia-Ting Feng; Lianjie Fu; Jun Zhao; Chengxiang Yang; Zhibin Yao; Jun Wang; Fei Wei (Engineering Geology, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

High efficient alkaline hydrogen evolution catalyzed by W2COx-Ru composite system containing bridged oxygen - Yu Dai; Hong Chuan Fu; Xiao Hui Chen; Qing Zhang; Ting Li; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

Species diversity and related ecology of chiggers on small mammals in a unique geographical area of Yunnan Province, southwest China - Yu Guo; Juan-Xiu Zhou; Xian-Guo Guo; Wen-Yu Song; Cheng-Fu Zhao; Zhi-Wei Zhang; Rong Fan; Ting Chen; Yan Lv; Peng-Wu Yin; Dao-Chao Jin (Experimental and Applied Acarology, 2023)

Two-point-one-line modularized strategy combined with Holliday-junction button probes for multiloci SNPs long-range distribution analysis - Wang Luo; You Wu; Xueping Chen; Li Zhang; Li Wang; Dan Bai; Qian Liu; Ting Wang; Hongyan Yu; Yaxing Xie; Yixin Fu; Zhongzhong Wang; et al. (Chemical Engineering Journal, 2023)

Anodic oxidation-accelerated self-reconstruction of tri-metallic Prussian blue analogue toward robust oxygen evolution reaction performance - Thi Xuyen Nguyen; Kai-Hsiang Yang; Yan-Jia Huang; Yen-Hsun Su; Oliver Clemens; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Genome-wide analysis of the MdZR gene family revealed MdZR2.2-induced salt and drought stress tolerance in apple rootstock - Keting Li; Longmei Zhai; Sitong Fu; Ting Wu; Xinzhong Zhang; Xuefeng Xu; Zhenhai Han; Yi Wang (Plant Science, 2023)

Petrogenesis and tectonic implications of the early Paleozoic granites in the Lincang granitic batholith, southwestern China: Constraints from geochronology, geochemistry and Hf isotopes - Qian R. Xiao; Qiang Wang; Zhong Y. Liu; Fu H. Xiong; Lei Fan; Han Zhao; Ting T. Gong (Ore and Energy Resource Geology, 2023)

Host shift promotes divergent evolution between closely related holoparasitic species - Jiayin Zhang; Zihao Huang; Weirui Fu; Chi Zhang; Ting Zan; Peng Nan; Linfeng Li; Zhiping Song; Wenju Zhang; Ji Yang; Yuguo Wang (Molecular Phylogenetics and Evolution, 2023)

Tracing surface water pollution in China’s supply chain - Siao Sun; Megan Konar; Qiuhong Tang; Guangtao Fu; Chuanglin Fang; Jing Wang; Yong Ni; Ting Ma (Journal of Hydrology, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Structural analysis of shield machine cutting monopile using p-y curve based finite element method - Ting Li; Bo Liu; Yanhui Han; Chunqing Fu; Yanding Sun (Computers and Geotechnics, 2023)

A high-resolution inventory of ammonia emissions from agricultural fertilizer application and crop residue in Taiwan - Chia-Hua Hsu; Fang-Yi Cheng; Chi-Ling Chen; Dong-Hong Wu; Tzu-Ying Chen; Kuo-Fu Liao; Wen-Lung Lay; Yi-Ting Zhang (Atmospheric Environment, 2023)

Spatial-temporal patterns and influencing factors for pulmonary tuberculosis transmission in China: an analysis based on 15 years of surveillance data - Xiao Wei; Ting Fu; Di Chen; Wenping Gong; Shuyuan Zhang; Yong Long; Xubin Wu; Zhongjun Shao; Kun Liu (Environmental Science and Pollution Research, 2023)

Integrative analysis uncovers the mechanism underlying the environmental adaptation of an indigenous crucian carp (Carassius auratus gibelio) in Dong's Rice Fish Duck System - Mingkun Luo; Xianbo Zhang; Wenbin Zhu; Qianwen Min; Jinli Hu; Jianjun Fu; Xiulan Shi; Bingjie Jiang; Yating Gong; Lanmei Wang; Ting Liu; Zaijie Dong (Aquaculture, 2023)

Assessing the occurrence and sources of synthetic additive pollutants in lake sediments using fecal and sewage markers - Rui Du; Xiaoxia Feng; Pu Wang; Ruiqiang Yang; Gang Li; Jianjie Fu; Yong Liang; Ting Ruan; Guibin Jiang (Environmental Pollution, 2023)

Hsa-miR-195-5p Inhibits Autophagy and Gemcitabine Resistance of Lung Adenocarcinoma Cells via E2F7/CEP55 - Linhai Fu; Zhupeng Li; Yuanlin Wu; Ting Zhu; Zhifeng Ma; Lingjun Dong; Jianyi Ding; Chu Zhang; Guangmao Yu (Biochemical Genetics, 2023)

Essential oil diversity of Cinnamomum parthenoxylon (Jack) Meisner from China - Fengying Qiu; Haikuan Yang; Chao Fu; Songsong Zhou; Yajing Sheng; Ting Zhang (South African Journal of Botany, 2023)

The crosstalk effects of polybrominated diphenyl ethers on the retinoic acid and thyroid hormone signaling pathway - Bin Zhang; Fu Chen; Ting Xu; Yijun Tian; Yajie Zhang; Miao Cao; Xueping Guo; Daqiang Yin (Science of The Total Environment, 2023)

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Utilization of constructed wetland technology in China's sponge city scheme under carbon neutral vision - Yamei Cai; Yaqian Zhao; Ting Wei; Wei Fu; Cheng Tang; Yujie Yuan; Qi Yin; Cong Wang (Journal of Water Process Engineering, 2023)

Characterization of microbial contamination of retail washed and unwashed shell eggs in Taiwan - Shu-Chen Hsu; Hsiu-Ling Chen; Chin-Fu Chou; Wen-Chun Liu; Chen-Ting Wu (Food Control, 2023)

Modulating the interfacial built-in electric field in oxygen vacancies-enriched Ru/MxOy@C (M = V, Nb, Ta) ordered macroporous heterojunctions for electrocatalytic hydrogen production - Xiao Hui Chen; Hong Chuan Fu; Xiao Lin Li; Ting Li; Qing Zhang; Zi Qing Li; Yuan Hao Luo; Jing Lei Lei; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Identification and Pathogen Stimulation Patterns of Neuronal Nitric Oxide Synthase (nNOS) in Black Rockfish (Sebastes schlegelii) - Xu Yan; Ningning Wang; Min Cao; Chao Li; Ning Yang; Ting Xue; Qiang Fu; Lin Song (Journal of Ocean University of China, 2023)

Asymmetric impact of natural resources rent, monetary and fiscal policies on environmental sustainability in BRICS countries - Haoliang Fu; Wenwei Guo; Zheng Sun; Ting Xia (Resources Policy, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Effect of tea polyphenols on sturgeon myofibrillar protein structure in the in vitro anti-glycation model mediated by low temperature vacuum heating - Dan-li Jin; Jian-ling Wei; Fan-yu He; Ting-ting Chai; Shao-tian Ren; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2023)

Cadmium exposure induces histological damage and cytotoxicity in the cardiovascular system of mice - Shing-Hsien Chou; Hung-Chen Lin; Shao-Wei Chen; Yu-Ting Tai; Shih-Ming Jung; Fu-Hsiang Ko; Jong-Hwei Su Pang; Pao-Hsien Chu (Food and Chemical Toxicology, 2023)

Control performance of bioretention system on non-point source pollution in typical Chinese rural areas of Southeastern China - Dafang Fu; Ting Pan; Chen Xu; Junyu Zhang (Ecological Engineering, 2023)

Viscosity-triggered near-infrared fluorescence nanoprobe for in vivo non-invasive diagnosis of cancer - Wen-Juan Fu; Jian Ting Li; Wen Hui Qian; Xiang Ying Zhang; Dan Dan Ma; Yu Ting Wang; Qi Jia Zhang; Dong Zhu (Chemical Engineering Journal, 2023)

Effect of foliar spraying of organic and inorganic selenium fertilizers during different growth stages on selenium accumulation and speciation in rice - Zhengqing Yuan; Weixiong Long; Ting Liang; Menghan Zhu; Aoyun Zhu; Xiaoyun Luo; Lu Fu; Zhongli Hu; Renshan Zhu; Xianting Wu (Plant and Soil, 2023)
Aims Most crops are supplemented with selenium (Se) through the exogenous addition of inorganic Se fertilizer. There is a lack of in-depth research on organic Se fertilizers. Meanwhile, the dosage range between human Se deficiency and Se toxicity is narrow, so the Se content of agricultural products needs to be controlled within a reasonable interval. Methods Se accumulation and speciation in rice were analyzed and compared during three different growth stages (late tillering stage, initiate heading stage, and full heading stage) using three Se fertilizers: selenite, fermented Se, and potassium selenocyanoacetate (Se-AAF) via the foliar application. Results The Se content in rice sprayed with organic Se fertilizer was controlled in the relatively safe range and met the human Se supplement requirement compared to the sprayed sodium selenite, which was too high of a dose. The percentage of organic Se and protein Se in brown rice was found to be similar in all three Se fertilizers. The highest organic Se content of 91.57% was found in the grain of rice at the full heading stage by spraying Se-AAF. The main Se species in the grain was selenomethionine (SeMet), which reached 80% of the total Se. Se-methyl selenocysteine(SeMeCys) was found only in Se-AAF. The grain quality showed that all three Se fertilizers increased the consistency of gelatinization. Conclusions Appropriately delaying the spraying time and selecting organic Se fertilizer as the Se source can help to produce green and safe selenium-rich rice.

Occurrence and ecological risk assessment of 16 phthalates in surface water of the mainstream of the Yangtze River, China - Jia-Nan Ren; Ning-Zheng Zhu; Xiang-Zhou Meng; Chong-Jing Gao; Kai Li; Li-Min Jin; Ting-Ting Shang; Fang-Ting Ai; Ming-Hong Cai; Jian-Fu Zhao (Environmental Science and Pollution Research, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Ellagic acid induces apoptosis and autophagy in colon cancer through the AMPK/mTOR pathway - Xiong Ni; Fu-Sheng Shang; Ting-Feng Wang; De-Jun Wu; Da-Gui Chen; Biao Zhuang (Tissue and Cell, 2023)

Molecular identification of a flavone synthase I/flavanone 3β-hydroxylase bifunctional enzyme from fern species Psilotum nudum - Jie Fu; Piao-Yi Wang; Rong Ni; Jiao-Zhen Zhang; Ting-Ting Zhu; Hui Tan; Jing Zhang; Hong-Xiang Lou; Ai-Xia Cheng (Plant Science, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

An iron-doped carbon fiber membrane as the microbe-electrode interaction accelerator for wastewater energy conversion - Ting Xu; Yifan Gao; Ni Yan; Boya Fu; Mengxi Yin; Xia Huang; Chengwen Wang; Xiaoyuan Zhang (Resources, Conservation and Recycling, 2023)

Efficient acquisition of high-purity cyanidin-3-O-glucoside from mulberry fruits: An integrated process of ATPS whole-cell transformation and semi-preparative HPLC purification - Yi-Tong Li; Ting Huang; Jin-Zheng Wang; Cheng-Hai Yan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Chemistry, 2023)

Perfluorooctanoic acid induces tight junction injury of Sertoli cells by blocking autophagic flux - Yuan Yang; Guoqing Fu; Xueyi Zhao; Xiaoping Wu; Kaili Zhu; Shangyu Liu; Ding Yuan; Jie Wu; Ting Wang; Changcheng Zhang; Haixia Zhao (Food and Chemical Toxicology, 2023)

Carnosic acid attenuated cytochrome c release through the mitochondrial structural protein Mic60 by PINK1 in SH-SY5Y cells - Chia-Yuan Lin; Yi-Chen Huang; Chi-Rei Wu; Han-Ting Wu; Ru-Huei Fu; Chia-Wen Tsai (Food and Chemical Toxicology, 2023)

Assessing the impact of rockfall on a bridge by using hybrid DEM/FEM analysis: A case study in Central Taiwan - Terry Y.P. Yuen; Meng-Chia Weng; Yu-Yao Fu; Guan-Ting Lu; Wen-Jie Shiu; Cheng-An Lu; Chun-Yuan Liu; Chia-Chi Chiu; Tzu-Han Wen (Engineering Geology, 2023)

Rigorous determination of pore size non-uniformity for nanofiltration membranes by incorporating the effects on mass transport - Ruo-yu Fu; Ting Zhang; Xiao-mao Wang (Desalination, 2023)

UV-Laser ablation enhanced Joule-heating catalyst support for electrified MSR in microreactor - Xinying Li; Ding Yuan; Tian Xie; Quancong Zhang; Wenjun Xu; Ting Fu; Xuyang Chu; Tao Luo; Linjing Wu; Wei Zhou (Chemical Engineering Journal, 2023)

Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Qi-Long-Tian capsule alleviates pulmonary fibrosis development by modulating inflammatory response and gut microbiota - Qiang Zhang; Ting Luo; Dezheng Yuan; Jing Liu; Yi Fu; Jiali Yuan (Functional & Integrative Genomics, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Comparative Transcriptome Analysis Identifies MAPK Signaling Pathway Associated with Regulating Ovarian Lipid Metabolism during Vitellogenesis in the Mud Crab, Scylla paramamosain - Yuanhao Ren; Wei Wang; Yin Fu; Zhiqiang Liu; Ming Zhao; Likun Xu; Tianyong Zhan; Ting Huang; Minghao Luo; Wei Chen; Chunyan Ma; Fengying Zhang; et al. (Fishes, 2023)
The mud crab, Scylla paramamosain, has abundant nutrients in the ovary, where numerous lipids accumulate during ovarian maturation. However, the mechanism behind the accumulation of lipids in the ovary of mud crab during ovarian maturation is largely unknown. This study conducted a comparative transcriptome analysis of the ovaries of mud crabs at various stages of ovarian maturation. A total of 63.69 Gb of clean data was obtained, with a Q30 of 93.34%, and 81,893 unigenes were identified, including 10,996 differentially expressed genes (DEGs). After KEGG enrichment of these DEGs, MAPK signaling pathway was significantly enriched during vitellogenesis. Moreover, the expression levels of genes involved in carbohydrate, amino acid, and lipid metabolism were found to be higher during vitellogenesis. The two genes (Sp-Eip75B and Sp-Eip78C) that are homologous to the vertebrate gene PPARγ in the PPAR signaling pathway, were identified. Additionally, genes in MAPK signaling pathway might regulate lipid metabolism through PPAR signaling pathway based on Protein-Protein Interaction (PPI) network. These findings suggest that MAPK signaling pathway plays a critical role in lipid metabolism in the ovary during vitellogenesis, which provides new insights into the mechanism of lipid accumulation during ovarian maturation in mud crabs.

Curbing per- and polyfluoroalkyl substances (PFASs): First investigation in a constructed wetland-microbial fuel cell system - Bin Ji; Yaqian Zhao; Yang Yang; Qiwen Li; Ying Man; Yunv Dai; Jingmiao Fu; Ting Wei; Yiping Tai; Xiaomeng Zhang (Water Research, 2023)

Development mechanism of radial chain rockbursts in a deep tunnel excavated by TBM - Lianjie Fu; Xia-Ting Feng; Zhibin Yao; Lei Hu; Yongwei Quan; Bin Lv; Wenjing Niu; Wei Zhang (Engineering Geology, 2023)

Boosting wastewater bioelectricity recovery via solvent mediation and zinc fencing: Dual regulation for catalyst spatial structure and active sites - Mengxi Yin; Tengfei Ren; Ting Xu; Boya Fu; Xiaoxin Cao; Xia Huang; Xiaoyuan Zhang (Chemical Engineering Journal, 2023)

The growth-regulating factor PdbGRF1 positively regulates the salt stress response in Populus davidiana × P. bolleana - Zhong-Yuan Liu; Ya-Ting Han; Chun-Yao Wang; Xiao-Jin Lei; Yuan-Yuan Wang; Wen-Fang Dong; Qing-Jun Xie; Yu-Jie Fu; Cai-Qiu Gao (Plant Science, 2023)

Dysregulation of Circulatory Levels of lncRNAs in Parkinson’s Disease - Ting Huang; Jin-Ying Zhao; Rong-Rong Pan; Teng Jiang; Xin-Xin Fu; Qing Huang; Xi-Xi Wang; Peng-Yu Gong; You-Yong Tian; Ying-Dong Zhang (Molecular Neurobiology, 2023)

The self-powered electrochemical biosensing platform with multi-amplification strategy for ultrasensitive detection of microRNA-155 - Yong-ping Gao; Ke-jing Huang; Fu-ting Wang; Yang-yang Hou; Lu-di Zhao; Bo-ya Wang; Jing Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Quantitative lateral flow immunoassay for rapid detection of procollagen type I N-terminal propeptide in the monitoring of osteoporosis treatment - Chung-An Chen; Ping-Yeh Chiu; Tse-Hao Huang; Natalie Yi-Ju Ho; Fu-Cheng Kao; Tsung-Ting Tsai (Analytica Chimica Acta, 2023)

Visualizing Seizure Propagation in Freely-moving Mice via Miniature Two-photon Microscopy - Zhuoran Zhang; Shihe Jiang; Kaibin Shi; Yan Li; Wei-Na Jin; Qiang Liu; Ting Zhao; Heping Cheng; Fu-Dong Shi (Neuroscience Bulletin, 2022)

Antifungal and Antibiofilm In Vitro Activities of Ursolic Acid on Cryptococcus neoformans - Wen-Jing Wang; Chan-Chan Liu; Yan-Tong Li; Miao-Qian Li; Yu-Ting Fu; Xin-Chen Li; Jie-Kang; Wei-Dong Qian (Current Microbiology, 2022)

Do carbon emission trading scheme policies induce green technology innovation? New evidence from provincial green patents in China - Lina Fu; Yang Yi; Ting Wu; Ruiwen Cheng; Zuoming Zhang (Environmental Science and Pollution Research, 2022)

Study on the seasonal variations of dimethyl sulfide, its precursors and their impact factors in the Bohai Sea and North Yellow Sea - Yu Guo; Liying Peng; Zishi Liu; Xiaoting Fu; Guicheng Zhang; Ting Gu; Danyang Li; Jun Sun (Frontiers in Marine Science, 2022)
Dimethyl sulfide (DMS) is one of the most important volatile biogenic sulfur compounds and plays a significant role in global climate change. Studying the seasonal variations and the environmental factors that affect the concentration of DMS would aid in understanding the biogeochemical cycle of sulfur compounds. Using benzene-assisted photoionization positive ion mobility spectrometry (BAPI-PIMS), the seasonal distribution and the key impact factors of DMS and dimethylsulfoniopropionate (DMSP) in the Bohai Sea and North Yellow Sea were investigated in the summer and autumn of 2019. The concentrations of DMS and its precursors, DMSPp and DMSPd, in the surface seawater were 0.11–23.90, 0.67–41.38, and 0.03–12.28 nmol/L, respectively, in summer, and 0.10–20.79, 0.39–13.51, and 0.18–20.58 nmol/L, respectively, in autumn. The air-to-sea exchange flux of DMS was 43.05 ± 44.52 and 34.06 ± 63.38 μmol/(m·d), respectively, in summer and autumn. The results demonstrated that the temperature was the most dominant environmental factor, and the abundance of dinoflagellates was the most dominant biological factor that affected the distribution of DMS and DMSP in summer. The abundance of diatoms was the most dominant biological factor, and the levels of PO 4 3- , NO 2 - , NO 3 - , and SiO 3 2- were the dominant environmental factors that affected the distribution of DMS and DMSP in autumn. These results of this study would be of great significance in understanding the biochemical cycle of DMS in BS and NYS.

Lead Exposure in Developmental Ages Promotes Aβ Accumulation by Disturbing Aβ Transportation in Blood-Cerebrospinal Fluid Barrier/Blood–Brain Barriers and Impairing Aβ Clearance in the Liver - Can-Can Zhou; Xu-Jie Wang; Zi-Chen Li; Wen-Jie Lu; Yun-Ting Zhang; Fu-Ming Shen; Dong-Jie Li (Biological Trace Element Research, 2022)

Exploitation of the antifungal and antibiofilm activities of plumbagin against Cryptococcus neoformans - Weidong Qian; Wenjing Wang; Jianing Zhang; Yuting Fu; Qiming Liu; Xinchen Li; Ting Wang; Qian Zhang (Biofouling, 2022)

Study on Iron Extraction from High Iron Bauxite Residue by Pyrite Reduction - HuiJun Fu; GuoZhi Lv; Ting-an Zhang; Xi Chao; Yang Chen (Bulletin of Environmental Contamination and Toxicology, 2022)

Performances of Evaporation and Desiccation Cracking Characteristics for Attapulgite Soils - Ting Yang; Xuguang Xing; Wei Fu; Xiaoyi Ma (Journal of Soil Science and Plant Nutrition, 2022)

Efficient seismic data reconstruction based on Geman function minimization - Yan-Yan Li; Li-Hua Fu; Wen-Ting Cheng; Xiao Niu; Wan-Juan Zhang (Applied Geophysics, 2022)

Diel variation in anti-predation behavior of a ground squirrel and relationships between vigilance and escape - Ling-Ying Shuai; Mei-Ting Liu; A.-Ping Zhu; Yuan-Yuan Cao; Fu-Shun Zhang (Behavioral Ecology and Sociobiology, 2022)

The altered functional modular organization in systemic lupus erythematosus: an independent component analysis study - Zheng-Ye Cao; Na Wang; Hua Wei; Jie-Ting Jia; Hong-Ying Zhang; Song-An Shang; Qing-Qiang Zhu; Xian-Fu Luo; Jing-Tao Wu (Brain Imaging and Behavior, 2022)

Spatially-explicit quantitative relationship for a potential PES mechanism: Cascade hydropower development in Yarlung Zangbo River Basin, China - Xiao-kang Zhu; Bin Fu; Ramon Felipe Bicudo Da Silva; Ying-man Guo; Chan-yuan Qin; Ting Feng; Hai-bing Yu; Kuang Xiao (Journal of Mountain Science, 2022)

Effect of paeonol against bacterial growth, biofilm formation and dispersal of Staphylococcus aureus and Listeria monocytogenes in vitro - Qiao Zeng; Yuting Fu; Min Yang; Ting Wang; Ying Wang; Shenghua Lv; Weidong Qian (Biofouling, 2022)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

Genome-Wide Identification and Expression Profiling of the bHLH Transcription Factor Gene Family in Saccharum spontaneum Under Bacterial Pathogen Stimuli - Ahmad Ali; Talha Javed; Uroosa Zaheer; Jing-Ru Zhou; Mei-Ting Huang; Hua-Ying Fu; San-Ji Gao (Tropical Plant Biology, 2021)

Cytological and morphology characteristics of natural microsporogenesis within Camellia oleifera - Xiaoyu Zhang; Hailang Tong; Zhiqiang Han; Long Huang; Jing Tian; Zhixing Fu; Yunyi Wu; Ting Wang; Deyi Yuan (Physiology and Molecular Biology of Plants, 2021)

Emergent chikungunya fever and vertical transmission in Yunnan Province, China, 2019 - XiaoXiong Yin; Ting-Song Hu; HaiLin Zhang; YongHua Liu; ZhiJian Zhou; LeBin Liu; Ping Li; YiYin Wang; ZhaoLan Yang; Jing Yu; SiYu Chen; Fu-Qiang Zhang (Archives of Virology, 2021)

The Combined Effects of Increased pCO2 and Warming on a Coastal Phytoplankton Assemblage: From Species Composition to Sinking Rate - Yuanyuan Feng; Fei Chai; Mark L. Wells; Yan Liao; Pengfei Li; Ting Cai; Ting Zhao; Feixue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
In addition to ocean acidification, a significant recent warming trend in Chinese coastal waters has received much attention. However, studies of the combined effects of warming and acidification on natural coastal phytoplankton assemblages here are scarce. We conducted a continuous incubation experiment with a natural spring phytoplankton assemblage collected from the Bohai Sea near Tianjin. Experimental treatments used a full factorial combination of temperature (7 and 11°C) and pCO 2 (400 and 800 ppm) treatments. Results suggest that changes in pCO 2 and temperature had both individual and interactive effects on phytoplankton species composition and elemental stoichiometry. Warming mainly favored the accumulation of picoplankton and dinoflagellate biomass. Increased pCO 2 significantly increased particulate organic carbon to particulate organic phosphorus (C:P) and particulate organic carbon to biogenic silica (C:BSi) ratios, and decreased total diatom abundance; in the meanwhile, higher pCO 2 significantly increased the ratio of centric to pennate diatom abundance. Warming and increased pCO 2 both greatly decreased the proportion of diatoms to dinoflagellates. The highest chlorophyll a biomass was observed in the high pCO 2 , high temperature phytoplankton assemblage, which also had the slowest sinking rate of all treatments. Overall, there were significant interactive effects of increased pCO 2 and warming on dinoflagellate abundance, pennate diatom abundance, diatom vs. dinoflagellates ratio and the centric vs. pennate ratio. These findings suggest that future ocean acidification and warming trends may individually and cumulatively affect coastal biogeochemistry and carbon fluxes through shifts in phytoplankton species composition and sinking rates.

In vitro anti-biofilm efficacy of sanguinarine against carbapenem-resistant Serratia marcescens - Yuting Fu; Wanting Liu; Miao Liu; Jianing Zhang; Min Yang; Ting Wang; Weidong Qian (Biofouling, 2021)

Combining targeted sequencing and ultra-low-pass whole-genome sequencing for accurate somatic copy number alteration detection - Junfeng Fu; Weihua Guo; Cheng Yan; Zhenyang Lv; Yu Wang; Ze Wang; Zhe Fan; Ting Lei (Functional & Integrative Genomics, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

YAP/TAZ affects the development of pulmonary fibrosis by regulating multiple signaling pathways - Ting Zhu; Zhifeng Ma; Haiyong Wang; Xiaoxiao Jia; Yuanlin Wu; Linhai Fu; Zhupeng Li; Chu Zhang; Guangmao Yu (Molecular and Cellular Biochemistry, 2020)

Pan-genome analysis of Paenibacillus polymyxa strains reveals the mechanism of plant growth promotion and biocontrol - Liangliang Zhou; Ting Zhang; Shan Tang; Xueqin Fu; Shuijing Yu (Antonie van Leeuwenhoek, 2020)

A sensitive and rapid bacterial antibiotic susceptibility test method by surface enhanced Raman spectroscopy - Shijie Fu; Xiwen Wang; Ting Wang; Zhiping Li; Deming Han; Chunsheng Yu; Cui Yang; Han Qu; Hang Chi; Yutian Wang; Song Li; Baihui Tian; et al. (Brazilian Journal of Microbiology, 2020)

Antifungal, anti-inflamatory and neuritogenic activity of newly-isolated compounds from Disporopsis aspersa - Fang-Li Gang; Feng Zhu; Chao-Fu Yang; Xiao-Ting Li; Hua Yang; Ming-Xia Sun; Wen-Jun Wu; Ji-Wen Zhang (Natural Product Research, 2020)

Retrieval of cotton plant water content by UAV-based vegetation supply water index (VSWI) - Shuobo Chen; Yinwen Chen; Junying Chen; Zhitao Zhang; Qiuping Fu; Jiang Bian; Ting Cui; Yizhe Ma (International Journal of Remote Sensing, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Global Profiling of Alternative Splicing in Callus Induction of Immature Maize Embryo - Xuemei Du; Ting Fang; Yan Liu; Liying Huang; Xiaoli Wang; Jie Zhang; Yangbo Cui; Maosen Zang; Guoying Wang; Junjie Fu; Yunjun Liu (In Vitro Cellular & Developmental Biology - Plant, 2020)

Physical Model Experimental Study on Spalling Failure Around a Tunnel in Synthetic Marble - Guo-Qiang Zhu; Xia-Ting Feng; Yang-Yi Zhou; Zheng-Wei Li; Lian-Jie Fu; Yong-Run Xiong (Rock Mechanics and Rock Engineering, 2020)

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

Adjuvant therapy with Astragalus membranaceus for post-stroke fatigue: a systematic review - Li Xu; Xiao-Yan Xu; Xue-Qin Hou; Fu-Gang Wang; Shan Gao; Han-Ting Zhang (Metabolic Brain Disease, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Spatial variation of the relationship between transport accessibility and the level of economic development in Qinghai-Tibet Plateau, China - Xue-ting Yang; Xiao-ping Qiu; Yi-ping Fang; Yun Xu; Fu-biao Zhu (Journal of Mountain Science, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

First report of lettuce big-vein associated varicosavirus infecting lettuce in China - Guo-Hua Zheng; Ting Ye; Fu-Rong Liao; Wen-Zhu Zhang; Yan-Lin Ming (Journal of Plant Pathology, 2019)

Pyrosequencing of nirS gene revealed spatial variation of denitrifying bacterial assemblages in response to wetland desertification at Tibet plateau - Yun-fu Gu; Ting Liu; Yan Bai; Quan-ju Xiang; Xiao-ping Zhang; Qiang Chen (Journal of Mountain Science, 2019)

Characterization and complete genomic analysis of two Salmonella phages, SenALZ1 and SenASZ3, new members of the genus Cba120virus - Ling Chen; Guoye Guan; Quan Liu; Shengjian Yuan; Tingwei Yan; Linyu Tian; Yan Zhou; Yixuan Zhao; Yingfei Ma; Ting Wei; Xiongfei Fu (Archives of Virology, 2019)

Dexamethasone protects the glycocalyx on the kidney microvascular endothelium during severe acute pancreatitis - Wen-qiao Yu; Shao-yang Zhang; Shui-qiao Fu; Qing-hui Fu; Wei-na Lu; Jian Zhang; Zhong-yan Liang; Yun Zhang; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2019)

Cerebrospinal fluid otorrhea secondary to congenital inner ear dysplasia: diagnosis and management of 18 cases - Bing Wang; Wen-jia Dai; Xiao-ting Cheng; Wen-yi Liuyang; Ya-sheng Yuan; Chun-fu Dai; Yi-lai Shu; Bing Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Different CO2 acclimation strategies in juvenile and mature leaves of Ottelia alismoides - Wen Min Huang; Hui Shao; Si Ning Zhou; Qin Zhou; Wen Long Fu; Ting Zhang; Hong Sheng Jiang; Wei Li; Brigitte Gontero; Stephen C. Maberly (Photosynthesis Research, 2018)

A new abietane diterpenoid from the roots of Tripterygium regelii - Zhi-Hua Jiang; Yan-Ping Liu; Miao He; Jin-Hua Zhao; Ting-Ting Wang; Xing-Yang Feng; Hao Yue; Ren-Bo An; Yan-Hui Fu (Natural Product Research, 2018)

Sucrose signaling function on the formation and swelling of bulblets of Lilium sargentiae E.H. Wilson - Suping Gao; Yuan Zhu; Lingyun Zhou; Xiaofeng Fu; Ting Lei; Qibing Chen; Xiaofang Yu; Yonghong Zhou; Wenji Li; Ju Hu; Di Hu; Wenhui Si (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

PTEN inhibition enhances angiogenesis in an in vitro model of ischemic injury by promoting Akt phosphorylation and subsequent hypoxia inducible factor-1α upregulation - Lixia Xue; Jiankang Huang; Ting Zhang; Xiuzhe Wang; Jianliang Fu; Zhi Geng; Yuwu Zhao; Hao Chen (Metabolic Brain Disease, 2018)

The relative abundance of alkane‐degrading bacteria oscillated similarly to a sinusoidal curve in an artificial ecosystem model from oil‐well products - Guoqiang Li; Peike Gao; Bo Zhi; Bing Fu; Ge Gao; Zhaohui Chen; Mengli Gao; Mengmeng Wu; Ting Ma (Environmental Microbiology, 2018)
Summary Microbial phylogenetic diversity and species interactions in natural ecosystems have been investigated extensively, but our knowledge about their ecological roles, community dynamics and succession patterns is far from complete. This knowledge is essential to understand the complicated interactions of microorganisms in natural ecosystems. Here, an artificial ecosystem model of microorganisms was constructed from oil‐well products and cultivated in a chemostat to investigate the succession pattern of alkane‐degrading bacteria, a functional population in oil reservoirs. Their abundance was quantified by an improved qPCR technique. Our results showed that the phylogenetic structure of this artificial ecosystem model is stable during most of the chemostat cultivation process, while the genotype structure of alkane‐degrading bacteria containing alk B genes shifted and their relative abundance oscillated similarly to a sinusoidal curve, like the succession pattern of producers in the Lotka–Volterra model. These results suggest that some theoretical frameworks of macroecology may work well in microbial ecosystems and be an efficient tool to understand them.

Bioactive furanocoumarins from the stems and leaves of Clausena hainanensis - Yan-Lei Ma; Chao Zhang; Wan-Hui Zhao; Shi Shi; Dan-Nv He; Pan Zhang; Xiao-Hong Liu; Ting-Ting Han; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2018)

Multi-Objective Differential Evolution-Chaos Shuffled Frog Leaping Algorithm for Water Resources System Optimization - Guohua Fang; Yuxue Guo; Xin Wen; Xiaomin Fu; Xiaohui Lei; Yu Tian; Ting Wang (Water Resources Management, 2018)

Combined prednisone and levothyroxine improve treatment of severe thrombocytopenia in hepatitis B with compensatory cirrhosis accompanied by subclinical and overt hypothyroidism - Jing Xue; Ru Feng; Haixia Fu; Qian Jiang; Hao Jiang; Jing Lu; Hui Liu; Jingwen Wang; Ting Niu; Xin Wang; Yandi Xie; Hao Wang; et al. (Science China Life Sciences, 2018)

Phylogenetic analysis and antifouling potentials of culturable fungi in mangrove sediments from Techeng Isle, China - Xiao-Yong Zhang; Wen Fu; Xiao Chen; Mu-Ting Yan; Xian-De Huang; Jie Bao (World Journal of Microbiology and Biotechnology, 2018)

Spatiotemporal variability of precipitation during 1961–2014 across the Mongolian Plateau - Fu-ying Qin; Gen-suo Jia; Jie Yang; Yin-tai Na; Mei-ting Hou; Narenmandula (Journal of Mountain Science, 2018)

Methylation of secreted frizzled-related protein 1 (SFRP1) promoter downregulates Wnt/β-catenin activity in keloids - Jiaqi Liu; Huayu Zhu; Hongtao Wang; Jun Li; Fu Han; Yang Liu; Wanfu Zhang; Ting He; Na Li; Zhao Zheng; Dahai Hu (Journal of Molecular Histology, 2018)

Isolation and identification of bovine nasopharyngeal mucosal epithelial cells and establishment of cell models of acute infection by foot-and-mouth disease virus - Wan-fu Bai; Lu Li; Ting Zhang; Xiao-hu Su; Yong-wei Wang; Bing-wu Zhao; Tao Zhang; Huan-min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2018)

Study of the Peak Shear Strength of a Cement-Filled Hard Rock Joint - Cheng-Xue She; Fu-Ting Sun (Rock Mechanics and Rock Engineering, 2018)

Neural Stem Cell Transplantation Promotes Functional Recovery from Traumatic Brain Injury via Brain Derived Neurotrophic Factor-Mediated Neuroplasticity - Liu-Lin Xiong; Yue Hu; Piao Zhang; Zhuo Zhang; Li-Hong Li; Guo-Dong Gao; Xin-Fu Zhou; Ting-Hua Wang (Molecular Neurobiology, 2018)

Effects of altitude on county economic development in China - Fu-biao Zhu; Yi-ping Fang; Xue-ting Yang; Xiao-ping Qiu; Hu Yu (Journal of Mountain Science, 2018)

Physiological and biochemical responses of Camellia sinensis to stress associated with Empoasca vitis feeding - Jian-yu Li; Meng-zhu Shi; Jian-wei Fu; Yue-chao He; David J. Perović; Ting Wang (Arthropod-Plant Interactions, 2018)

Gradient effect of road transportation on economic development in different geomorphic regions - Xue-ting Yang; Yi-ping Fang; Xiao-ping Qiu; Fu-biao Zhu (Journal of Mountain Science, 2018)

Brg1 inhibits E-cadherin expression in lung epithelial cells and disrupts epithelial integrity - Ting Wang; Wenjing Zou; Chao Niu; Fengxia Ding; Yaping Wang; Shuang Cai; Hua Zhu; Daiyin Tian; Jihong Dai; Enmei Liu; Qing Lu; Zhou Fu; et al. (Journal of Molecular Medicine, 2017)

Coamorphous Loratadine-Citric Acid System with Enhanced Physical Stability and Bioavailability - Jin Wang; Ruimiao Chang; Yanan Zhao; Jiye Zhang; Ting Zhang; Qiang Fu; Chun Chang; Aiguo Zeng (AAPS PharmSciTech, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Preferential flow characteristics of reclaimed mine soils in a surface coal mine dump - Lv Gang; Li Jun; Li Yexin; Wang Ting; Liu Yazhuo; Fu Xinyang (Environmental Monitoring and Assessment, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

Future Science Prize goes to non-invasive prenatal testing - Kang Li; Yaou Duan; Magdalene Yin Lin Ting; Zhiying Ou; Li Liu; Kang Zhang; Xin Fu (Science China Life Sciences, 2017)

Triptolide Promotes the Clearance of α-Synuclein by Enhancing Autophagy in Neuronal Cells - Guanzheng Hu; Xiaoli Gong; Le Wang; Mengru Liu; Yang Liu; Xia Fu; Wei Wang; Ting Zhang; Xiaomin Wang (Molecular Neurobiology, 2017)

High‐frequency daily temperature variability in China and its relationship to large‐scale circulation - Fu‐Ting Wu; Congbin Fu; Yun Qian; Yang Gao; Shu‐Yu Wang (International Journal of Climatology, 2017)
Two measures of intra‐seasonal variability, indicated respectively by standard deviations ( SD ) and day‐to‐day ( DTD ) fluctuations denoted by absolute differences between adjacent 2‐day periods, as well as their relationships with large‐scale circulation patterns were investigated in China during 1962–2008 on the basis of homogenized daily temperature records from 549 local stations and reanalysis data. Our results show that both the SD and DTD of daily minimum temperatures ( T min ) in summer as well as the minimum and maximum temperatures in winter have been decreasing, while the daily maximum temperature ( T max ) variability in summer is fluctuating more, especially over southern China. In summer, an attribution analysis indicates that the intensity of the Western Pacific Subtropical High ( WPSH ) and high‐level East Asian Subtropical Jet stream ( EASJ ) are positively correlated with both SD and DTD , but the correlation coefficients are generally greater with the SD than with the DTD of the daily maximum temperature, T max . In contrast, the location of the EASJ shows the opposite correlation pattern, with intensity regarding the correlation with both SD and DTD . In winter, the Arctic Oscillation ( AO ) is negatively correlated with both the SD and DTD of the daily minimum temperature, but its intra‐seasonal variability exhibits good agreement with the SD of the T min . The Siberian High acts differently with respect to the SD and DTD of the T min , demonstrating a regionally consistent positive correlation with the SD . Overall, the large‐scale circulation can well explain the intra‐seasonal SD, but DTD fluctuations may be more local and impacted by local conditions, such as changes in the temperature itself, the land surface, and so on.

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Di-2-ethylhexyl phthalate induced oxidative damage involving FasL-associated apoptotic pathway in mouse spermatogenic GC-2spd cells - Xiao Tang; Kun Tong; Lishan Zhu; Guoqing Fu; Wei Chang; Ting Zhou; Zhibing Zhang; Ling Tong; Ling Zhang; Yuqin Shi (Molecular & Cellular Toxicology, 2016)

Application of high resolution SNP arrays in patients with congenital oral clefts in south China - TING-YING LEI; HONG-TAO WANG; FAN LI; YING-QIU CUI; FANG FU; RU LI; CAN LIAO (Journal of Genetics, 2016)

Mineral and pore structure characteristics of gas shale in Longmaxi formation: a case study of Jiaoshiba gas field in the southern Sichuan Basin, China - Liang Wang; Yonghong Fu; Jun Li; Liqiang Sima; Qingzhao Wu; Wujun Jin; Ting Wang (Arabian Journal of Geosciences, 2016)

Trade-offs between carbon sequestration, soil retention and water yield in the Guanzhong-Tianshui Economic Region of China - Xiaonan Yang; Zixiang Zhou; Jing Li; Xin Fu; Xingmin Mu; Ting Li (Journal of Geographical Sciences, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Effect of Lactobacillus Strains on Intestinal Microflora and Mucosa Immunity in Escherichia coli O157:H7-Induced Diarrhea in Mice - Xin Bian; Ting-ting Wang; Min Xu; Smith Etareri Evivie; Guang-Wen Luo; Hong-zhang Liang; Shang-fu Yu; Gui-Cheng Huo (Current Microbiology, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Impact of misplaced subclavian vein catheter into jugular vein on transpulmonary thermodilution measurement variables - Wen-qiao Yu; Yun Zhang; Shao-yang Zhang; Zhong-yan Liang; Shui-qiao Fu; Jia Xu; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2016)

Cloning, expression, and characterization of Pseudomonas vesicularis MA103 β-1,3-xylanase in Escherichia coli ClearColi BL21(DE3) - Wen-Sing Liang; Tsuei-Yun Fang; Hong-Ting Lin; Tristan C. Liu; Wen-Jung Lu; Wen-Shyong Tzou; Shye-Jye Tang; Fu-Pang Lin; Shiu-Mei Liu; Chorng-Liang Pan (Fisheries Science, 2015)

Effect of β-glucan on stress tolerances and biocontrol efficacy of Cryptococcus laurentii against Penicillium expansum in pear fruit - Da Fu; Lizhen Zeng; Xiaodong Zheng; Ting Yu (BioControl, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Multiple Mesozoic magma processes formed the 240–185 Ma composite Weishan pluton, South China: evidence from geochronology, geochemistry, and Sr-Nd isotopes - Xing Ding; Wei-Dong Sun; Wei-Feng Chen; Pei-Rong Chen; Tao Sun; Sai-Jun Sun; Chiou-Ting Lin; Fu-Kun Chen (International Geology Review, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Surface Properties and In Vitro Bioactivity of Fluorapatite/TiO2 Coatings Deposited on Ti Substrates by Nd:YAG Laser Cladding - Chi-Sheng Chien; Yu-Sheng Ko; Tsung-Yuan Kuo; Tze-Yuan Liao; Huan-Chang Lin; Tzer-Min Lee; Ting-Fu Hong (Journal of Medical and Biological Engineering, 2015)

Immune protective effect of human alpha-1-antitrypsin gene during β cell transplantation in diabetic mice - Lu Yang; Yu-Ting Liao; Xiao-Fei Yang; Li-Wei Reng; Hui Qi; Fu-Rong Li (Immunologic Research, 2015)

A Meta-analysis of the Effects of Experimental Warming on Plant Physiology and Growth on the Tibetan Plateau - Gang Fu; Zhen-Xi Shen; Wei Sun; Zhi-Ming Zhong; Xian-Zhou Zhang; Yu-Ting Zhou (Journal of Plant Growth Regulation, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

The Effects and Mechanism of miR-92a and miR-126 on Myocardial Apoptosis in Mouse Ischemia-Reperfusion Model - Changhao Jiang; Ningning Ji; Gaojiang Luo; Shimao Ni; Jinbo Zong; Zhili Chen; Donglai Bao; Xinyan Gong; Ting Fu (Cell Biochemistry and Biophysics, 2014)

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration - Da Su; Faisal Sultan; Ning-chun Zhao; Bing-ting Lei; Fu-biao Wang; Gang Pan; Fang-min Cheng (Journal of Zhejiang University-SCIENCE B, 2014)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

SNAP25 Ameliorates Sensory Deficit in Rats with Spinal Cord Transection - Wei Wang; Fang Wang; Jia Liu; Wei Zhao; Qi Zhao; Mu He; Bao-Jiang Qian; Yang Xu; Ran Liu; Su-Juan Liu; Wei Liu; Jin Liu; et al. (Molecular Neurobiology, 2014)

The toxicity of cerium nitrate to Elodea canadensis: subcellular distribution, chemical forms and physiological effects - Wei Yue Chu; San Juan Cai; Yong Yang Fu; Fei Fei Li; Ting Xu; Han Qiu; Qin Song Xu (Acta Physiologiae Plantarum, 2014)

Structure–activity relationships of anthocyanidin glycosylation - Chang Ling Zhao; Zhong Jian Chen; Xue Song Bai; Can Ding; Ting Ju Long; Fu Gang Wei; Kang Ru Miao (Molecular Diversity, 2014)

The Application of Water Quality Monitoring Data in a Reservoir Watershed Using AMOS Confirmatory Factor Analyses - Edward Ming-Yang Wu; Chia Cheng Tsai; Juey Fu Cheng; Shu Lung Kuo; Wei Ting Lu (Environmental Modeling & Assessment, 2014)

A new naphthalene glycoside from the sponge-derived fungus Arthrinium sp. ZSDS1-F3 - Jun-Feng Wang; Fu-Quan Xu; Zhen Wang; Xin Lu; Jun-Ting Wan; Bin Yang; Xue-Feng Zhou; Tian-Yu Zhang; Zheng-Chao Tu; Yonghong Liu (Natural Product Research, 2014)

Improved Insecticidal Toxicity by Fusing Cry1Ac of Bacillus thuringiensis with Av3 of Anemonia viridis - Fu Yan; Xing Cheng; Xuezhi Ding; Ting Yao; Hanna Chen; Wenping Li; Shengbiao Hu; Ziquan Yu; Yunjun Sun; Youming Zhang; Liqiu Xia (Current Microbiology, 2014)

Investigating soil moisture sensitivity to precipitation and evapotranspiration errors using SiB2 model and ensemble Kalman filter - Xiaolei Fu; Zhongbo Yu; Lifeng Luo; Haishen Lü; Di Liu; Qin Ju; Tao Yang; Feng Xu; Huanghe Gu; Chuanguo Yang; Jingwen Chen; Ting Wang (Stochastic Environmental Research and Risk Assessment, 2014)

Deep transcriptome sequencing of rhizome and aerial-shoot in Sorghum propinquum - Ting Zhang; Xiuqin Zhao; Wensheng Wang; Liyu Huang; Xiaoyue Liu; Ying Zong; Linghua Zhu; Daichang Yang; Binying Fu; Zhikang Li (Plant Molecular Biology, 2014)

Spatial and temporal plasticity of synaptic organization in anterior cingulate cortex following peripheral inflammatory pain: multi-electrode array recordings in rats - Yun-Fei Lu; Yan Wang; Ying He; Fu-Kang Zhang; Ting He; Rui-Rui Wang; Xue-Feng Chen; Fei Yang; Ke-Rui Gong; Jun Chen (Neuroscience Bulletin, 2014)

Bioaccumulation, subcellular, and molecular localization and damage to physiology and ultrastructure in Nymphoides peltata (Gmel.) O. Kuntze exposed to yttrium - Yongyang Fu; Feifei Li; Ting Xu; Sanjuan Cai; Weiyue Chu; Han Qiu; Sha Sha; Guangyu Cheng; Qinsong Xu (Environmental Science and Pollution Research, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Better environmental data may reverse conclusions about niche‐ and dispersal‐based processes in community assembly - Li-Wan Chang; David Zelený; Ching-Feng Li; Shau-Ting Chiu; Chang-Fu Hsieh (Ecology, 2013)
Variation partitioning of species composition into components explained by environmental and spatial variables is often used to identify a signature of niche‐ and dispersal‐based processes in community assembly. Such interpretation, however, strongly depends on the quality of the environmental data available. In recent studies conducted in forest dynamics plots, the environment was represented only by readily available topographical variables. Using data from a subtropical broad‐leaved dynamics plot in Taiwan, we focus on the question of how would the conclusion about importance of niche‐ and dispersal‐based processes change if soil variables are also included in the analysis. To gain further insight, we introduced multiscale decomposition of a pure spatial component [c] in variation partitioning. Our results indicate that, if only topography is included, dispersal‐based processes prevail, while including soil variables reverses this conclusion in favor of niche‐based processes. Multiscale decomposition of [c] shows that if only topography was included, broad‐scaled spatial variation prevails in [c], indicating that other as yet unmeasured environmental variables can be important. However, after also including soil variables this pattern disappears, increasing importance of meso‐ and fine‐scaled spatial patterns indicative of dispersal processes.

Global transcriptome analysis and identification of a CONSTANS-like gene family in the orchid Erycina pusilla - Ming-Lun Chou; Ming-Che Shih; Ming-Tsair Chan; Shih-Yi Liao; Chen-Tran Hsu; Yao-Ting Haung; Jeremy J. W. Chen; Der-Chih Liao; Fu-Hui Wu; Choun-Sea Lin (Planta, 2013)

Response of ecosystem respiration to experimental warming and clipping at daily time scale in an alpine meadow of tibet - Gang Fu; Zhen-xi Shen; Xian-zhou Zhang; Cheng-qun Yu; Yu-ting Zhou; Yun-long Li; Peng-wan Yang (Journal of Mountain Science, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Increased expression of actin filament-stabilizing protein tropomyosin after rat traumatic brain injury - Xinmin Wu; Hongran Fu; Feihui Zou; Wei Jin; Ting Xu; Peipei Gong; Jian Xu; Yaohua Yan; Gang Cui; Kaifu Ke; Yilu Gao; Chunfeng Liu; et al. (Journal of Molecular Histology, 2013)

Tetrodotoxin attenuates isoproterenol-induced hypertrophy in H9c2 rat cardiac myocytes - Ming-Zi Chen; Qing-Ting Bu; Shu-Chao Pang; Feng-Lan Li; Mei-Na Sun; Er-Fu Chu; Hui Li (Molecular and Cellular Biochemistry, 2012)

The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2012)

RETRACTED ARTICLE: A 2-D DIGE analysis of simulated acid rain-responsive proteins in Pinus massoniana needles - Ting-Wu Liu; Wen-Jun Hu; Xiao-Qin Wang; Li Niu; Bin Fu; Fei-Hua Wu; Zhen-Ming Pei; Hai-Lei Zheng (Trees, 2012)

The cell-specific upregulation of bone morphogenetic protein-10 (BMP-10) in a model of rat cortical brain injury - Yaohua Yan; Peipei Gong; Wei Jin; Jian Xu; Xiaohong Wu; Ting Xu; Qinglei Hang; Hongran Fu; Kaifu Kei; Yilu Gao (Journal of Molecular Histology, 2012)

Pyrosequencing of a short fragment of the amelogenin gene for gender identification - Shujin Li; Ting Feng; Lihong Fu; Zhenhua Li; Chunguang Lou; Xiaojing Zhang; Chunling Ma; Bin Cong (Molecular Biology Reports, 2012)

Increased expression of BAG-1 in rat brain cortex after traumatic brain injury - Ting Xu; Xueqian Wang; Maohong Cao; Xinmin Wu; Yaohua Yan; Hongran Fu; Wei Zhao; Peipei Gong; Kaifu Ke; Xingxing Gu (Journal of Molecular Histology, 2012)

The monitoring results of electromagnetic radiation of 110-kV high-voltage lines in one urban location in Chongqing P.R. China - Qi-zhong Qin; Yu Chen; Ting-ting Fu; Li Ding; Ling-li Han; Jian-chao Li (Environmental Monitoring and Assessment, 2012)

Comparative Metabolite Profiling and Hormone Analysis of Perennial and Annual Rice - Xiuqin Zhao; Ting Zhang; Liyu Huang; Huimin Wu; Fengyi Hu; Fan Zhang; Linghua Zhu; Binying Fu (Journal of Plant Biology, 2012)

Analysis of ESTs from a Normalized cDNA Library of the Rhizome Tip of Oryza longistaminata - Ting Zhang; Lijuan Li; Fengyi Hu; Xiuqin Zhao; Binying Fu; Daichang Yang (Journal of Plant Biology, 2012)

Diallyl disulfide induces Ca2+ mobilization in human colon cancer cell line SW480 - Chung-Yi Chen; Chien-Fu Huang; Ya-Ting Tseng; Soong-Yu Kuo (Archives of Toxicology, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

The Reanalysis of Currents and Throughflow Volume Transport in the Taiwan Strait - Ting Yu; Zengan Deng; Guijun Han; Xinrong Wu; Hongli Fu; Kejian Wu (Marine Geodesy, 2012)

Bp5250 inhibits vascular endothelial growth factor-induced angiogenesis and HIF-1α expression on endothelial cells - Kuan-Ting Lin; Jin-Cherng Lien; Ching-Hu Chung; Sheng-Chu Kuo; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

A high-frequency cyclic secondary somatic embryogenesis system for Cyclamen persicum Mill - Cui Rong You; Ting Jun Fan; Xue Qin Gong; Fu Hua Bian; Li Kun Liang; Fu Ning Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

17beta-estradiol attenuates pressure overload-induced myocardial hypertrophy through regulating caveolin-3 protein in ovariectomized female rats - Yu-Hong Cui; Zhi Tan; Xiao-Dong Fu; Qiu-Ling Xiang; Jin-Wen Xu; Ting-Huai Wang (Molecular Biology Reports, 2011)

Inhibitory Effect of Delphinidin on Monocyte–Endothelial Cell Adhesion Induced by Oxidized Low-Density Lipoprotein via ROS/p38MAPK/NF-κB Pathway - Chun-ye Chen; Long Yi; Xin Jin; Ting Zhang; Yu-jie Fu; Jun-dong Zhu; Man-tian Mi; Qian-yong Zhang; Wen-hua Ling; Bin Yu (Cell Biochemistry and Biophysics, 2011)

Soil phosphorus fractions and tree phosphorus resorption in pine forests along an urban-to-rural gradient in Nanchang, China - Xiao-Fei Hu; Fu-Sheng Chen; Gregory Nagle; Yun-Ting Fang; Ming-Quan Yu (Plant and Soil, 2011)

Overexpression of a 10-deacetylbaccatin III-10 β-O-acetyltransferase gene leads to increased taxol yield in cells of Taxus chinensis - Peng Zhang; Shu-Tao Li; Ting-Ting Liu; Chun-Hua Fu; Peng-Peng Zhou; Chun-Fang Zhao; Long-Jiang Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Overexpression of survivin and cyclin D1 in CHO cells confers apoptosis resistance and enhances growth in serum-free suspension culture - Xinghui Zhao; Junwei Guo; Yingqun Yu; Shaoqiong Yi; Ting Yu; Ling Fu; Lihua Hou; Wei Chen (Biotechnology Letters, 2011)

Emerging threat of thrips-borne Melon yellow spot virus on melon and watermelon in Taiwan - Jui-Chu Peng; Shyi-Dong Yeh; Li-Hsin Huang; Ju-Ting Li; Yuan-Fu Cheng; Tsung-Chi Chen (European Journal of Plant Pathology, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Anticancer Drug-Loaded Nanospheres Based on Biodegradable Amphiphilic ε-Caprolactone and Carbonate Copolymers - Guo-Ping Yan; Rong-Feng Zong; Liang Li; Ting Fu; Fan Liu; Xiang-Hua Yu (Pharmaceutical Research, 2010)

Two cotton Cys2/His2-type zinc-finger proteins, GhDi19-1 and GhDi19-2, are involved in plant response to salt/drought stress and abscisic acid signaling - Gang Li; Fu-Ju Tai; Yong Zheng; Juan Luo; Si-Ying Gong; Ze-Ting Zhang; Xue-Bao Li (Plant Molecular Biology, 2010)

The impact of naturalized legumes on plant communities in Northern Taiwan: are we worrying too much? - Jenn-Kuo Tsai; Hao-Ting Sun; Chiao-Fen Chen; Chang-Fu Hsieh; Shan-Huah Wu (Plant Ecology, 2010)

Osteogenic role of endosomal chloride channels in MC3T3-E1 cells - Huan Wang; Na Huo; Feifei Li; Shanmin Fu; Yang Xue; Ting Yang; Xuan Wen; Yin Ding; Xiaohong Duan (Molecular and Cellular Biochemistry, 2010)

Total estrogenic activity and nonylphenol concentration in the Donggang River, Taiwan - Meei-Fang Shue; Fu-An Chen; Ting-Chien Chen (Environmental Monitoring and Assessment, 2010)

Patterns of plant invasions in China: Taxonomic, biogeographic, climatic approaches and anthropogenic effects - Shan-Huah Wu; Hao-Ting Sun; Yung-Ching Teng; Marcel Rejmánek; Shu-Miaw Chaw; T.-Y. Aleck Yang; Chang-Fu Hsieh (Biological Invasions, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Free radical scavenging activity and antiproliferative potential of Polygonum cuspidatum root extracts - Yun-Wei Lin; Fu-Jung Yang; Chia-Ling Chen; Wei-Ting Lee; Ruey-Shyang Chen (Journal of Natural Medicines, 2010)

Risk of digoxin intoxication caused by clarithromycin–digoxin interactions in heart failure patients: a population-based study - Agnes L. F. Chan; Meng-Ting Wang; Chen-Yi Su; Fu-Hsiung Tsai (European Journal of Clinical Pharmacology, 2009)

Pancreas-specific protein disulfide isomerase has a cell type-specific expression in various mouse tissues and is absent in human pancreatic adenocarcinoma cells: implications for its functions - Xin-Miao Fu; Xiangchen Dai; Jian Ding; Bao Ting Zhu (Journal of Molecular Histology, 2009)

Cytoplasmic male sterility with self-incompatibility, a novel approach to utilizing heterosis in rapeseed (Brassica napus L.) - Jin-xiong Shen; Han-zhong Wang; Ting-dong Fu; Bao-ming Tian (Euphytica, 2008)

Improving ovary and embryo culture techniques for efficient resynthesis of Brassica napus from reciprocal crosses between yellow-seeded diploids B. rapa and B. oleracea - Jing wen; Jin-xing Tu; Zai-yun Li; Ting-dong Fu; Chao-zhi Ma; Jin-xiong Shen (Euphytica, 2008)

Gene transfer into primary cultures of fetal neural stem cells by a recombinant adenovirus carrying the gene for green fluorescent protein - Yong Fu; Shen-qing Wang; Ying-peng Liu; Guo-peng Wang; Jian-ting Wang; Shu-sheng Gong (Journal of Zhejiang University-SCIENCE B, 2008)

Mitochondrial DNA Distinction of Northeastern China Roe Deer, Siberian Roe Deer, and European Roe Deer, to Clarify the Taxonomic Status of Northeastern China Roe Deer - Chao-Ting Xiao; Ming-Hai Zhang; Yan Fu; Hung-Son Koh (Biochemical Genetics, 2007)

Prediction of heterosis using QTLs for yield traits in rapeseed (Brassica napus L.) - Jin-Xiong Shen; Ting-Dong Fu; Guang-Sheng Yang; Jin-Xing Tu; Chao-Zhi Ma (Euphytica, 2006)

Identification and characterization of piggyBac-like elements in the genome of domesticated silkworm, Bombyx mori - Han-Fu Xu; Qing-You Xia; Chun Liu; Ting-Cai Cheng; Ping Zhao; Jun Duan; Xing-Fu Zha; Shi-Ping Liu (Molecular Genetics and Genomics, 2006)

Molecular validation of multiple allele inheritance for dominant genic male sterility gene in Brassica napus L - Lai-Qiang Song; Ting-Dong Fu; Jin-Xing Tu; Cao-Zhi Ma; Guang-Sheng Yang (Theoretical and Applied Genetics, 2006)

Identification of differentially expressed genes in Tetrahymena thermophila in response to dichlorodiphenyltrichloroethane (DDT) by suppression subtractive hybridization - Wei Miao; Ting Yu; Eduardo Orias; Mingliang Wan; Chenjie Fu (Environmental Microbiology, 2006)
Summary The insecticide dichlorodiphenyltrichloroethane (DDT) is persistent in the environment, and continues to cause health problems. Tetrahymena has potential as a model organism for assaying low levels of DDT and for analysing the mechanisms of its toxicity. We constructed the suppression subtractive hybridization library of T. thermophila exposed to DDT, and screened out 90 Expressed Sequence Tags whose expressions were significantly up‐ or downregulated with DDT treatment. From this, a series of important genes related to the DDT metabolism and detoxification were discovered, such as P450 gene, glutathione S‐transferase gene and sterol carrier protein 2 gene. Furthermore, their expressions under different concentrations of DDT treatment were detected by real‐time fluorescent quantitative PCR. The results show that Tetrahymena is a relevant and useful model organism for detecting DDT in the environment and for discovering biomarkers that can be used to develop specific bio‐reporters at the molecular and genomic levels.

Inheritance of seed colour and identification of RAPD and AFLP markers linked to the seed colour gene in rapeseed (Brassica napus L.) - Liu Zhi-wen; Fu Ting-dong; Tu Jin-xing; Chen Bao-yuan (Theoretical and Applied Genetics, 2005)

Genetic structure of endangered Rhodiola sachalinensis - Ting-Fen Yan; Yuan-Gang Zu; Xiu-Feng Yan; Fu-Jun Zhou (Conservation Genetics, 2003)

New Method to Obtain Ultrasonic Angle Independent Doppler Color Images Using a Sector Transducer - Ding-Yu Fei; Cai-Ting Fu (Annals of Biomedical Engineering, 1999)